Experimental study on mechanical properties of double-layer damped liquid storage tanks with various isolation devices - Xiang Li; Lei Xu; Fa Yang; Li-jie Zhu; Bo-lin Wang; Zheng Lu (Soil Dynamics and Earthquake Engineering, 2026)

Cytokinin represses NH4+ efflux by suppressing GH3.5 transcription through an ARR10/12-dependent pathway - Ting-Ting Li; Chi-Shang Luan; Li Zhang; Meng Wang; Herbert J. Kronzucker; Chuan-Fa Liu; Ping Lan; Yunqi Liu; Weiming Shi; Dong-Wei Di (Journal of Plant Physiology, 2026)

In-situ phase transformation induced carboxyl protection boosts stability and activity of bismuth-based photocatalysts for CO2 reduction - Jiehao Li; Ying Liu; Shuoqing Qi; Biao Wu; Yi-lei Li; Jun Yang; Qian Wang; Ying-juan Hao; Fa-tang Li (Journal of Environmental Chemical Engineering, 2026)

Green extraction of vanadium pentoxide from industrial solid wastes and its electrochemical calcium storage performance - Hainan Li; Jiaqi Lv; Xi Luo; Zimeng Qu; Feng Liu; Yuehong Zhang; Pengfei Wang; Fa-Nian Shi; Jiyan Liang; Yuhan Wu (Journal of Environmental Chemical Engineering, 2026)

Engineering a robust glucose oxidase: Enhanced thermostability, acid tolerance and catalytic activity drive high-level gluconic acid production - Ying-Zhi Peng; Xin-Cheng Jiang; Jing Li; Yi-Fa Yu; Jia-Yu He; Bing-Yan Xu; Xiang Lv; Qiong-Ying Wu; Shuai You; Jun Wang (Food Chemistry, 2026)

Ultrathin polyacrylonitrile/cellulose nanofiber/hydroxyapatite composite separator regulating desolvation and ion flux for aqueous zinc-ion batteries - Xu-qiao Hu; Li-li Du; Qi-qun Lei; Shuang Zou; Fa-nian Shi; Yu-han Wu; Yu-hang Zhang; Zhe Gong; Peng-fei Wang (Chemical Engineering Journal, 2026)

Hierarchical core–shell nanoplatforms based on sacrificial template-directed ZnO2@ZIF-8 for spatiotemporally controlled and self-augmented chemodynamic–photothermal antibacterial therapy - Yi-Fei Hui; Duan-Ping Hu; Yi Zhao; Shulin Li; Zhi-Feng Cai; Lin-Yi Li; Yuming Xie; Yong-Nian Zeng; Zu-Jin Lin; Fa-Qiang Tang (Chemical Engineering Journal, 2026)

Interannual variability of secondary organic carbon driven by seasonal shifts in formation regimes in southern Taiwan - Jun-Fa Ye; Chih-Yu Chan; Jian-Xian Wu; Shi-Ya Tang; Tse-Lun Chen; Li-Hao Young; Yu-Chieh Ting; Yen-Ping Peng; Wei-Hsiang Chen; Ming-Yeng Lin; Si-Chee Tsay; Neng-Huei Lin; et al. (Atmospheric Environment, 2026)

Dynamics and drivers of CO2 emissions in agricultural river-ditch networks: management and wetland degradation effects - Xia Li; Xiao-Dong Li; Si-Liang Li; Shi-Yuan Ding; Wan-Fa Wang; Li Bai; Min Xiao; Ming-Guo Wang; Xiao-Long Liu (Applied Geochemistry, 2026)

Attribute-probability-constrained facies-consistent ES-MDA geostatistical inversion for acoustic impedance - Zhi-Fang Ran; Guo-Fa Li; Hao Li; Wei-Wei Gu; Yin-Quan Hao (Applied Geophysics, 2026)

Retraction notice to “Vegetation restoration strategies based on plant water use patterns” [Sci. Total Environ. 924 (2024) 171611] - Juan Gui; Zongxing Li; Fa Du; Xiaoyin Liu; Jian Xue (Science of The Total Environment, 2026)

Phenylbutene dimers and saturated phenylbutene derivatives from Zingiber montanum with anti-inflammatory potential - Zhi-hang Wu; Lu Chen; Jin-na Zhao; Lv-you Wan; Fa-xiang Guo; Lei Zhang; Li-bo Wang; Jin-hui Wang; Xian-mei Piao (Phytochemistry, 2026)

Interlayer phosphate architectonics in porous organic cages enable ultrafast and high-capacity seawater uranium extraction - Wansheng Zhang; Yangyang Xin; Tong Qi; Yining Wang; Fengwei Li; Yun Fa; Huizhou Liu (Journal of Hazardous Materials, 2026)

Regulation mechanism of N2O and CH4 emissions during the pig manure composting amended with Polygonum Multiflorum Thunb - Ya-jun Duan; Hong-sheng Wu; Jiang-yu Yang; Zheng-tong Zhou; Tao-ran Shi; Cheng Cheng; Zhen-wei Li; Chun-fa Wu; Ming-chun Di; Yu-dong He; Feng-yi Hu (World Journal of Microbiology and Biotechnology, 2026)

Elevation-conditioned isotope diagnostics of seasonal reversals in surface water–suprapermafrost groundwater exchange in Tibetan Plateau headwaters - Fa Du; Zongxing Li; Juan Gui; Jian Xue; Ahui Zhang; Deyu Zhao (Journal of Hydrology, 2026)

Inoculation timing matters: Effective microorganisms enhance humification and reduce antibiotic resistance during composting - Guomin Li; Xiaoying Wang; Haosen Fa; Xu Bao; Chuntao Zhu; Bing Wang; Hong Jiang (International Biodeterioration & Biodegradation, 2026)

Assessing the impact of wind-wave misalignment on floating offshore wind turbine responses under rapid typhoon wind shifts - Zhitong Lv; Fa Li; Hao Wang; Shitang Ke; Xu Hong; Feng Hu; Tongguang Wang (Engineering Structures, 2026)

Experimental study on the seismic performance and design optimization of precast piers with various connection types - Xinlei Yang; Xiang Li; Fa Yang; Quanchang Ren; Jianbao Miao; Yantao Liu; Yukai Zhang; Qingtao Zheng (Bulletin of Earthquake Engineering, 2026)

TTI Anisotropic Tomographic Velocity Model Building Using Hamiltonian Polynomials - Hao Zheng; Guo-Fa Li; Xu-Hui Xu; Jie-Xiong Cai (Applied Geophysics, 2026)

Spatiotemporal changes of salt crusts in the Ebinur Lake Basin (2005–2025) using a non-linear spectral unmixing model - Chen-Wei Wang; Xiao-Xiao Zhang; Xiao-Ming Cao; Yi-Ming Feng; Jia-Qiang Lei; Sheng-Yu Li; Jia-Xiu Zou; Jie Zhou; Lian-You Liu; Zi-Fa Wang; Xiao Tang (Journal of Arid Environments, 2026)

Iron oxide-apatite and porphyry Cu–Au deposits controlled by pre-ore degassing, emplacement depths, and evaporite assimilation: A comparative study of the Nihe Fe and Shaxi Cu–Au deposits, Anhui, China - Yi Li; Ke-Zhang Qin; Le Wang; Guo-Xue Song; Tao-Fa Zhou; Yong-Jian Wang; Ming-Guo Zhai (Gondwana Research, 2026)

High entropy alloy PtRuCuCoNi nanosponges with tunable electronic configurations for electrocatalytic lactic acid oxidation toward upcycling waste polylactic acid - Bingshuo Li; Xiaokun Fa; Ruichen Geng; Liuyang Jiang; Ruiping Liu; Zhihan Zhang; Yinglong Wang; Shuli Yin (Chemical Engineering Journal, 2026)

Upcycling alumina industrial solid waste into vanadium disulfide anode materials for lithium-ion batteries - Runxin Zhang; Xuesong Li; Yuhan Wu; Feng Liu; Weishan Li; Pengfei Wang; Laishi Li; Fa-Nian Shi; Rui Xu; Yusheng Wu (Resources, Conservation and Recycling, 2026)

Source-specific VOCs and atmospheric oxidation capacity drive the formation of secondary aerosols and visibility impairment in East Asia suburban environments - Tse-Lun Chen; Kuan-Chieh Lee; Jun-Fa Yeh; Jian-Xian Wu; Li-Hao Young; Neng-Huei Lin; Si-Chee Tsay; Wen-Yinn Lin; Chia-Hsin Lin; Ta-Chih Hsiao (Journal of Hazardous Materials, 2026)

Effects of exogenous N-acyl-homoserine lactones on biofilm formation by denitrifying bacteria and denitrification start-up in sequencing batch biofilm reactors - Zhi-fei Li; Meng-yuan Yu; Jun-lin Li; Jun Xie; Xiang-ju Cheng; Wang-bao Gong; Kai Zhang; Guang-jun Wang; Yun Xia; Wen-ping Xie; Quan-fa Zhong; Hong-yan Li; et al. (Journal of Environmental Chemical Engineering, 2026)

Enhanced wastewater treatment performance in a two-stage pyrite-based denitrifying deep bed filter - Jun Ding; Feng Ling; Shu-Yang Tian; Wen-Bo Xie; Xiao-Cai Chen; Li Yu; Xu-Mei Li; Fa-Zhi Xie; Wei-Hua Li; Tong-Zhan Xue; Hou-Yun Yang; Xian-Huai Huang (Journal of Environmental Chemical Engineering, 2026)

Chronic exposure to low-dose cadmium disrupts spermatogenesis in mice through ectoplasmic specialization damage - Yue Li; Zi-Fa Li; Bo Qiu; Kai Chen; Tian-Lin Zhang; Hai-Peng Wang; Lin Wang (Journal of Environmental Sciences, 2026)

Moisture-driven ionogel neuromorphic sensor for apnea detection and event recognition in wearable patches - Xiu-juan Li; Fa Zhang; Ke-yan Li; Xin Li; Zhen-hui Tao; Ke-xin Wang; Zhen-yu Zhang; Guo Fang; Zi-xin Wang; Jia-yi Xie; Long Zhang; Chang-min Yu; et al. (Chemical Engineering Journal, 2026)

ICE1 plays a vital role in the development of pollen grains through regulating tapetum degradation and nutrient mobilization in Arabidopsis thaliana - Fa-Li Chang; Jer-Lun Kuo; Meng-Ting Wu; Ching-Hsing Liang; Shiang-Jiuun Chen; Chien-Chih Yang (Plant Molecular Biology, 2026)

Structure-Constrained Prior Ensembles for ES-MDA Post-Stack Acoustic Impedance Inversion - Zhi-fang Ran; Yin-quan Hao; Pin Zhang; Weiwei Gu; Guo-fa Li (Applied Geophysics, 2026)

Near-Surface Q-Factor Estimation Using a Non-Gaussian Energy Spectrum - Ze-lin Li; Jiang-nan Tong; Ya-nan Jiang; Tong Chen; Guo-fa Li (Applied Geophysics, 2026)

Model Regularization Techniques in Depth-Domain Tomographic Velocity model building - Hao Zheng; Guo-Fa Li; Jiang-Hua Zhang; Kai Guo; Jie-xiong Cai (Applied Geophysics, 2026)

Petrogenesis and tectonic implications of the Neoarchean metavolcanic rocks in the southeast Yinshan Block, north China Craton (NCC): Constraints from U–Pb–Hf–Nd isotopes and geochemistry - Zhongwei Shao; Zhuang Li; Chunjing Wei; Ze-Fa Wang; Cheng-Cheng Xue; Tian-Xiang Shi (Precambrian Research, 2026)

Guaianolide sesquiterpenoids from Chrysanthemum indicum L. alleviate rheumatoid arthritis by targeting of NLRP3 inflammasome pathway - Gui-Min Xue; Hao Feng; Dong-Rong Zhu; Xin-Xin Guo; Ding-Qiao Xu; Yan-Jun Sun; Yan-Le Zhi; Zhi-Qiang Zhang; Guo-Sheng Li; Fa-Wu Dong; Jin-Feng Xue (Phytochemistry, 2026)

Fe-Ni-MOF-derived NiFe2O4/NiO heterostructure for detection of 2-CEES at ppb level - Duo Zhang; Ying-Nan Dou; Rui Gao; Xian-Fa Zhang; Hui Zhao; Xiao-Li Cheng; Shan Gao; Ying-Ming Xu; Li-Hua Huo (Chemical Engineering Journal, 2026)

Multi‐Decadal Dynamics of Wetland Methane Emissions Revealed by Knowledge‐Guided Machine Learning - Qing Zhu; Kyle A. Arndt; Kunxiaojia Yuan; Fa Li; Qing Ying; Licheng Liu; Eric Ward; Avni Malhotra; Jianqiu Zheng; Fenghui Yuan; Sparkle L. Malone; Gavin McNicol; et al. (Global Change Biology, 2026)
Measurement of methane fluxes (FCH 4 ) from natural systems, such as wetlands, has lagged far behind carbon dioxide fluxes. Short and fragmented wetland FCH 4 data limit our ability to assess its long‐term dynamics and potential climate feedbacks. Extrapolating short‐term FCH 4 records to recent decades remains challenging for both process‐based models and data‐driven machine learning (ML) approaches. Here, we develop a knowledge‐guided ML framework that integrates eddy covariance (EC) FCH 4 observations, field warming experiments, and biogeochemical knowledge to reconstruct the long‐term FCH 4 budgets and trends. Focusing on the 11 longest EC monitoring sites in the AmeriFlux network, we found considerable variability in multi‐decadal trends of wetland FCH 4 , with increases up to 14% per decade from 2000 to 2024. We also found that the strength of these increasing trends declines from high to low latitudes, highlighting the vulnerability of northern wetlands. This work presents novel and robust reconstructions of long‐term wetland FCH 4 , offering critical benchmark datasets for bottom‐up ecosystem models and advancing fundamental understanding of wetland biogeochemistry.

Activating FcγRI inhibits RIG-I-mediated host antiviral innate immunity by FGR during PRRSV-ADE infection - Peng-li Xu; Yi-han Li; Fa-hao Li; Shi-jie Zhao; Wen Li; Jing Chen; Ping-an Xia; Yi-na Zhang (Veterinary Microbiology, 2026)

Opisoma menchikoffi Dubar, 1948: New occurrences from the Lower Jurassic of the High Atlas, Morocco and Tethyan Himalaya, southern Xizang (Tibet), China - Fu-Lin Li; Kai Ye; Xin Rao; Zhong Han; Cheng-Gang Wang; Xiong-Wei Zeng; Long Wang; Hao Liu; Zong-Xin Wang; Fa-Fu Wu; Kun Liang; Wen-Kun Qie (Palaeoworld, 2026)

Occurrence, ecological risk, and human health assessment of herbicide residues in Chaohu Lake, China - Yong-mei Zhang; Ping-ping Fan; Ling-zhi Zhang; Wei Yu; Song Xia; Fa-li Liu; Xue-de Li (Journal of Environmental Chemical Engineering, 2026)

Age–Sex Class Variation in the Activity Budget and Diet of Rhinopithecus bieti in Association with Monthly Temperature - Jacob B. Kraus; Zhi Pang Huang; Yan Pang Li; Liang Wei Cui; Shuang Jin Wang; Jin Fa Li; Feng Liu; Yun Wang; Karen B. Strier; Wen Xiao (International Journal of Primatology, 2026)
The energy and nutrient costs associated with body mass, age, and sex can influence variation in primate behavior and diet. However, comparatively little is known about how these factors affect the behavioral and dietary flexibility of Asian colobines in response to intra-annual climate shifts. We collected data on an isolated population of black-and-white snub-nosed monkeys ( Rhinopithecus bieti ) at Mt. Lasha in the Yunling Provincial Nature Reserve, Yunnan, China, using instantaneous and scan sampling across 32 months between May 2008 and August 2016 to assess the association of temperature on the activity budgets and diets among and within age-sex classes. Adult females spent more time feeding, juveniles spent more time moving and less time resting, and adult males spent less time moving and more time resting than other age-sex classes. We did not detect any significant variation in diet across age-sex classes. This population spent more time feeding and less time moving and resting in colder months than in warmer months; however, we only detected these temperature-related effects within age-sex classes for moving and resting, not feeding. This population also spent more time feeding on lichen during colder months than during warmer months, a finding that cannot be explained by temperature-related dietary shifts within age-sex classes because their diets remained stable throughout the year. Our results suggest that intra-annual variation in temperature may amplify the distinct physiological demands among different age-sex classes, leading to greater shifts in activity patterns than in diet composition.

Soil microplastics at different depths before and after mechanical harvesting: case study in Anhui Province, China - Shi-hao Zhao; Di Dai; Yu-xin Tan; Si-yao Li; Bing-yu Chen; Qian Wang; Long Chen; Ji-yue Wang; Shu-guang Zhu; Fa-zhi Xie (Environmental Monitoring and Assessment, 2026)

Who is the best allogeneic hematopoietic stem cell transplant donor for severe aplastic anemia? Data from the Chinese Bone Marrow Transplantation Registry Group (CBMTRG) - Zheng-Li Xu; Lan-Ping Xu; Shun-Qing Wang; De-Pei Wu; Xi Zhang; Su-Jun Gao; Ling-Hui Xia; Rui Xi; Jian-Min Yang; Qi-Fa Liu; Ming Jiang; Xiao-Sheng Fang; et al. (Science Bulletin, 2026)

A novel land surface temperature retrieval method using channel correlation for atmospheric parameter modeling from SDGSAT-1 data - Li-Qin Cao; Hang Zhao; Du Wang; Yan-Fei Zhong; Fa-Wang Ye (Remote Sensing of Environment, 2026)

High-resolution stalagmite records from Southwest China reveal a North Atlantic link to the 8.2 ka event - Xiao-Hua Shao; Xiao-Hong Zhao; Peng-Fa Li; Kan Zhao; Xing-Gong Kong; Yong-Jin Wang; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

The presence of microplastics in human semen and the protective role of nicotinamide mononucleotide against polystyrene nanoplastics-induced reproductive and early embryonic toxicity - Fa Ren; Jingliang Pei; Le Li; Di Yuan; Fengdan Hao; Pengyun Qiao; Yingdong Liu (Journal of Hazardous Materials, 2026)

Amorphous phosphate-mediated Schottky junction at Mo2N-based heterojunction interface to accelerate interfacial electron transfer for boosted photocatalytic hydrogen evolution - Yu-pei Li; Zi-xin Qi; Xiao-jing Wang; Jun Zhao; Jun Yang; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2026)

Three Decades in Review: The Evolution of Rockfall Impact Testing Apparatuses - Zhong-Min Ji; Huan-Huan Zhang; Haris Saroglou; Pavlos Asteriou; Ting-Hui Wang; Dong-Po Wang; Fa-Quan Wu; Zhen-Hua Li (Rock Mechanics and Rock Engineering, 2026)

Low-frequency signal inversion and reconstruction via the spatial structure regularization - Wei-wei Gu; Hao Li; Dong-feng Zhao; Peng-fei Wang; Guo-fa Li (Applied Geophysics, 2026)

Inhibiting browning in ready-to-eat oysters: The efficacy and mechanism of L-cysteine combined with light-proof nitrogen-filled packaging during accelerated storage - Ying Luo; Jie Xu; Shuo Lv; De-Yang Li; Yuan-Yuan Hu; Xiao-Yang Liu; Fa-Wen Yin; Da-Yong Zhou (Food Research International, 2026)

Dual efficient X-ray scintillation and strong second harmonic generation in a single cubic alkane Cu4I4 cluster achieved through organic-inorganic synergistic effect - Bao-Yi Li; Jun-Zhe Li; Wen-Fei Wang; Peng-Kun Wang; Rong Li; Shuai-Hua Wang; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2026)

Construction of a GdVO4-In2O3 n-n heterojunction enables ppb level triethylamine detection at low temperatures - Yi-Cheng Geng; Xiang-Bing Li; An-Qi Wang; Bing-Yi Xi; Qian-Qian Zhang; Li-He Yan; Fa-Ming Li; Wei-Dong Zhu (Chemical Engineering Journal, 2026)

Gene editing and association analysis of circadian clock gene TaPRR59 highlights its importance in yield-related traits in wheat - Jinrong Li; Meijie Zhu; Guimei Hu; Xiaoyue Chen; Huixian Xue; Yuanxun Zhang; Yifan Wang; Ziqi Li; Dengke Xu; Mingjun Zhai; Guangsheng Zhou; Chenxiao Cui; et al. (Theoretical and Applied Genetics, 2026)

Correction to: Subsurface structure-induced water use strategies mediate shrub-herb coexistence in soil-limited hillslopes - Zidong Luo; Yunpeng Nie; Jun Zhang; Fa Wang; Wenna Liu; Daoheng Zhuang; Jiajie Li; Hu Du; Hongsong Chen (Plant and Soil, 2026)

Subsurface structure-induced water use strategies mediate shrub-herb coexistence in soil-limited hillslopes - Zidong Luo; Yunpeng Nie; Jun Zhang; Fa Wang; Wenna Liu; Daoheng Zhuang; Jiajie Li; Hu Du; Hongsong Chen (Plant and Soil, 2026)

Integrative approaches to river ecosystem assessment and restoration: a review of methodologies and strategies for coherent implementation - Xian-bing Zhang; Shang Huang; Yu-peng Hu; Geng Li; Wen-jie Li; Sheng-fa Yang (Environmental Monitoring and Assessment, 2026)

Tracking seasonal variability in plant traits from spaceborne PRISMA and NEON AOP across forest types and ecoregions - Fujiang Ji; Ting Zheng; Alexey N. Shiklomanov; Ruqi Yang; Philip A. Townsend; Fa Li; Dalei Hao; Hamid Dashti; Kyle R. Kovach; Hangkai You; Junxiong Zhou; Min Chen (Remote Sensing of Environment, 2026)

An interpretable machine learning model for predicting p-y curves of monopiles in clay - Biao Li; Wen-Gang Qi; Yi-Fa Wang; Fu-Ping Gao; Lu Jing; Shun-Yi Wang; Ben He (Ocean Engineering, 2026)

From metamorphic to magmatic fluids: Decoding of Yanshanian Au mineralization process in the Wangu gold deposit, southern China - Yong-shun Li; Yong-jun Shao; Zhong-fa Liu; Ke Chen; Xue-ling Dai; Ming-hui Chen; Ming-peng He; Qing Gou (Journal of Asian Earth Sciences, 2026)

Toward noise-resilient retrieval of land surface temperature and emissivity using airborne thermal infrared hyperspectral imagery - Du Wang; Li-Qin Cao; Yu-Hao Du; Hai-Yang Xiong; Fa-Wang Ye; Yan-Fei Zhong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Study on browning mechanism of Antarctic krill meal during storage: based on the model system approach - Chao Guo; Xiang-Bo Zeng; Chang-Qiang Leng; De-Yang Li; Qian Wang; Fa-Wen Yin; Bei-Wei Zhu; Da-Yong Zhou (Food Chemistry, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Hyperspectral surface reflectance improves GPP estimation in terrestrial biosphere modeling using model-data fusion - Haoran Liu; Fa Li; Hamid Dashti; Min Chen (Remote Sensing of Environment, 2025)

Thermotolerance and antiapoptosis enhancement by Lycium barbarum polysaccharide: counteracting mitochondrial oxidative stress in human sperm exposed to decabromodiphenyl ether (BDE-209) at 37 °C - Pengyun Qiao; Le Li; Zilong Li; Feifan Sun; Fa Ren (Journal of Thermal Biology, 2025)

Injectable nanocomposite hydrogel with antibacterial/osteogenic dual functions for synergistic repair of infectious bone defects in hyperlipidemia microenvironment - Yongkai Wang; Yunhan Sun; Jiaming Song; Dongchen Fa; Yuting Qu; Jiayi Li; Xiao Fu; Li Ma (Chemical Engineering Journal, 2025)

Correction: Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Severe enterovirus A71 pathogenesis and immune responses in human nucleolin transgenic mice - Nien-En Hsiao; Ya-Fang Wang; Yi-Chen Lin; Wei-Ting Chou; Li-Jin Hsu; Shih-Min Wang; Jen-Ren Wang; Ming-Derg Lai; Shun-Hua Chen; Chuan-Fa Chang (Medical Microbiology and Immunology, 2025)

Different Intensities of Exercise Affect the Prognosis of Ventricular Aneurysm in Mice by Regulating the Progression of Cardiac Fibrosis - Rui-Qiang Qi; Juan Song; Hong-Bin Ma; Mei-Ling Nie; Liu-Hang Su; Cui-Lian Dai; Fa-Guang Zhou; Sui-Ji Li (Cardiovascular Toxicology, 2025)

Late Cenozoic Climates and Mountains Drove Diversification of the Pardosa laura Species Complex From Eastern China - Li‐Juan Liu; Dan Fu; Shu‐Qiang Li; Yu‐Fa Luo (Journal of Biogeography, 2025)
Aim To test how evolutionary processes of spiders in mountain ranges of eastern China were in response to environmental changes, we analyze the correlation between diversification of the Pardosa laura species complex (Araneae, Lycosidae) and historical climates and mountains in this region. Methods We reconstruct phylogenetic relationships and patterns of phylogeography and genetic diversity using mtDNA data from samples spanning the full range of the species complex P. laura in eastern China. Results The P. laura species complex clustered into four lineages: Lineage I includes five haplotypes from the areas to the north of the Yinshan‐Yanshan Mountains; Lineage II consists of 23 haplotypes from the areas between the Qinling Mountains–Huaihe River Line and the Nanling Mountains; Lineage III and IV are composed of 21 and 62 haplotypes, respectively, from the areas between the Yinshan‐Yanshan Mountains and the Nanling Mountains. Each lineage corresponds to that, grouped from haplotype network analyses, with the same geographic distribution areas. All four lineages initially diversified during about 1.43 and 0.24 Ma ago (Ma) in relation to the Pleistocene glacial‐inglacial cycles. The biogeographic reconstructions suggest that the species complex P. laura most likely originated in central China around 7.68 (11.17–4.85) Ma in relation to the recent ( approximately 8 Ma) expansion of grasslands and retraction of forests. The inter‐colony dispersal between central China and northeastern China occurred during the late Neogene, between around 7.68 and 3.14 Ma. Central China is an important dispersal center, with dispersal to southwestern and northern China between the late Pliocene and middle Pleistocene, approximately 3.14–2.89 and 2.89–1.43 Ma, respectively. Main Conclusions The contemporary genetic structure of the P. laura species complex presents a high correlation between lineages and geographic distribution. The historical phylogeographic patterns suggested that the late Cenozoic climate changes and the mountainous corridors and isolation events, as well as the lineage dispersals and ecological adaptations shaped the diversification of a spider species complex in eastern China over long timescales.

Sugar-based block copolymer/carbon nanotube nanocomposites for thermoelectric applications - Yen-Yu Chen; Hong Li; Chih-Jung Lin; Koshin Tanaka; Meng-Hao Lin; Shao-Huan Hong; Min-Chi Fu; Jian-Fa Ding; Yu-Jane Sheng; Redouane Borsali; Tsuyohiko Fujigaya; Cheng-Liang Liu (Chemical Engineering Journal, 2025)

Theaflavin 3,3′-digallate suppresses metastasis and reduces insulin-like growth factor-1-induced cancer stemness and invasiveness in human melanoma cells - Ju-Pi Li; Yi-Hsien Hsieh; Yi-Hsun Lee; Wen-Yi Tsai; Shun-Fa Yang; Yih-Shou Hsieh; Pei-Ni Chen (Chemico-Biological Interactions, 2025)

Taurine alleviates postovulatory oocyte aging via TBK1 associated mitophagy in pigs and mice - Fa-Li Zhang; Chen-Xi Gao; Wen-Wen Li; Ai-Ying Li; Lan Li; Wei Shen (Theriogenology, 2025)

A novel dual co-catalyst strategy using MXene and NCDs for boosting TiO2 photocatalytic efficiency under visible light - Caixia Li; Yuyang Chen; Fangyun Zhou; Suxiang Ge; Wenjun Fa; Weiwei He (Journal of Environmental Chemical Engineering, 2025)

Lipidomics revealed the geographical origin and breed variability of sheep milk - Hai-Long Wang; Xiaoyin Chen; Xiaoyu Peng; Yu Gao; Jiaqi Wang; Wei Li; Chinping Tan; Yuan fa Liu; Wenjun Zou; Yong-Jiang Xu (Food Bioscience, 2025)

Cadmium activated oxidative stress and endoplasmic reticulum stress pathway promote apoptosis in the common carp (Cyprinus carpio L.) brain - Jia Liu; Wei Lu; Zheng-yao Guo; Yue-hong Li; Wen-fa Lv (Fish & Shellfish Immunology, 2025)

Local collaboration between oxygen vacancy, palladium and platinum trimer triggers exceptional performance in the alkaline fuel cell - Dinesh Bhalothia; Che Yan; Yawei Wu; Jui-Cheng Kao; Yu-Chieh Lo; Haolin Li; Nozomu Hiraoka; Hirofumi Ishii; Yen-Fa Liao; Sheng Dai; Chen-Hao Wang; Alice Hu; et al. (Chemical Engineering Journal, 2025)

Synergistic self-assembly of anions and cations to construct colloidal MOFs-derived binder-free electrodes for superiorcapability - Jianlong Huang; Xi Wang; Kai Wang; Quan Zhang; Shuwan Zong; Wenhao Fa; Da Li; Aitang Zhang (Chemical Engineering Journal, 2025)

Water stable isotope evidence reveals the impact of soil thickness on mobile water recharge in Karst Hillslopes, Southwest China - Jun Zhang; Na Feng; Jiajie Li; Fa Wang; Kelin Wang; Hongsong Chen (Science China Earth Sciences, 2025)

Effects of Cyclic Stretch on Chondrogenic Differentiation of Rat Adipose-Derived Stem Cells Cultured on Type-I Collagen Coated PDMS Membrane - Hung-Maan Lee; Hui-Ying Li; Yi-Ho Hsieh; Lassina Barro; Ching-Yi Cheng; Ming-Fa Hsieh (Journal of Medical and Biological Engineering, 2025)

Formation of a DMM-EM2 Mixing Trend in Continental Intraplate Basalts by Variable Degrees of Melting of Hybrid Mantle Controlled by the Lithospheric Lid - Xun Yu; Gang Zeng; Xiao-Jun Wang; Fa-Jun Sun; Hui-Li Zhang (Journal of Earth Science, 2025)

Disruption of the SIRT1/PI3K/AKT Signaling Axis Mediates Fluoride-Induced Cardiotoxicity: Evidence from in Vitro and Zebrafish Models - Lei Guo; Bo Yang; Fa Chen; Xiaoshuang Yuan; Jinyang Cheng; Xiaoxu Chen; Ying Zhou; Xu Yang; Yanju Li; Yang Liu; Dongxin Tang; Feiqing Wang (Biological Trace Element Research, 2025)

Genomic characterization of Gillisia xinjiangensis sp. nov.: insights into nitrogen metabolism, stress adaptation, and application potential - Hao-hao Wang; Chi Zhang; Ya-qin Chen; Yi-fan Guo; Li-jian Ding; Sheng-fa Zhang; Gai-jun Du; Wei-yan Zhang; Shan He (Systematic and Applied Microbiology, 2025)

Vanadium-cobalt oxide nanoflower catalyst for efficient and stable overall water splitting in alkaline and seawater electrolytes - Yong-qi Tian; Song-lin Xu; Jia Li; Shuang-shuang Zhang; Bo-yao Zhang; Rong-da Zhao; Fu-fa Wu; De-peng Zhao (Next Research, 2025)

Aggregation pheromones of Bostrichidae: A review - Li Yu; Xiao-Lu Cao; Wei Zheng; Jun Li; Fa-Yang Xie; Xia-Lin Zheng (Journal of Stored Products Research, 2025)

Integrated multi-omics analysis uncovers Zearalenone-induced ovarian and intestinal inflammation is mediated by the tumor necrosis factor-α - Fa-Li Zhang; Ai-Ying Li; Ke-Xin Zhu; Kai Zhang; Zhe Tian; Tao Wang; Xin-Hao Zhang; Jian Zang; Xiao-Feng Sun; Wei Shen; Lan Li (Journal of Hazardous Materials, 2025)

Investigation on the influence of droplets on the flow characteristics and energy separation in vortex tube based on CFD analysis - Lijuan He; Zhong Zhou; Zhi Li; Jianzi Yang; Fa Zhang; Xingyu Meng; Wenxi You; Chenlei Zhao (International Journal of Refrigeration, 2025)

Influence of the strain rate on the deformation and failure of rocks with multiscale cracks - Yan-jie Feng; Cheng-zhi Qi; Fa Zhao; Tao Li; An-sen Gao; Xiao-yu Ma (Geomechanics for Energy and the Environment, 2025)

Cross-reactivity and conserved epitope analysis of tropomyosin from Lateolabrax japonicus and shellfish species - Meng-Si Li; Fei Xia; Qing-Mei Liu; Fa-Jie Li; Yu-Ni Liao; Li-Qiang Zhong; Gui-Xia Chen; Lian-Zhong Luo; Yi-Xiang Liu; Guang-Ming Liu (Food Chemistry, 2025)

Sensory characteristics and key odor-active compounds of oxidized Antarctic krill oil: A comparative study with oxidized fish oil - Gui-Mei Dong; Rui-Ying Wang; Fa-Wen Yin; De-Yang Li; Lei Qin; Da-Yong Zhou (Food Chemistry, 2025)

Environmental levels of bis(2-ethylhexyl)-tetrabromophthalate (TBPH) cause thyroid toxicity and early carcinogenic signals in juvenile fish - Xiang-sheng Hong; Liang Yan; Wei Sang; Wang Liu; Zhi-tong Li; Juan Wang; Sai-hong Yan; Jia-jing Xin; Gao-feng Zhao; Xu-fa Ma; Jin-miao Zha (Environmental Pollution, 2025)

Scalable and fast electrophoresis-accelerated assembly of chiroptical carbon fibers with multi functions - Haixing Jiao; Baiqi Song; Fa Li; Yuanhan Tang; Na Zhang; Xiaofang Zhang; Weilin Xu (Chemical Engineering Journal, 2025)

AdaptiveGS: an explainable genomic selection framework based on adaptive stacking ensemble machine learning - Zhen Yang; Mei Song; Xianggeng Huang; Quanrui Rao; Shanghui Zhang; Zhongzheng Zhang; Chenyang Wang; Wenjia Li; Ran Qin; Chunhua Zhao; Yongzhen Wu; Han Sun; et al. (Theoretical and Applied Genetics, 2025)

Soil water sources and transport modes based on stable isotope tracing in Northeastern Qinghai-Tibet Plateau - Juan Gui; Youjing Yuan; Zongxing Li; Qi Feng; Fa Du (Journal of Mountain Science, 2025)

Hysteretic temperature sensitivity in wetland CH4 emission modeling - Shuo Chen; Kunxiaojia Yuan; Fa Li; Qing Zhu; Qianlai Zhuang (Agricultural and Forest Meteorology, 2025)

Establishment and characterization of a new Chinese extrahepatic cholangiocarcinoma cell line, EBC-X1 - Yuanhui Su; Huan Tang; Xin Miao; Cheng Yu; Changpeng Chai; Wei Huang; Lu Li; Jieyu Zheng; Tao Xu; Fa Jin; Zhipeng Ye; Zhao Hu; et al. (Human Cell, 2025)

Leveraging transfer learning and leaf spectroscopy for leaf trait prediction with broad spatial, species, and temporal applicability - Fujiang Ji; Fa Li; Hamid Dashti; Dalei Hao; Philip A. Townsend; Ting Zheng; Hangkai You; Min Chen (Remote Sensing of Environment, 2025)

Targeted discovery of oxygen-bridged sesquiterpenes from Cinnamomum migao by MS/MS-based molecular networking and their neuroprotective activities - Lang Zhou; Xiong Pan; Fa-ju Chen; Mei Peng; Yu Wang; Ming Gao; Li-shou Yang; Liang-qun Li; Juan Yang; Xiao-sheng Yang; Qi-ji Li (Phytochemistry, 2025)

Real-time assessment of PM1.0-bound trace metal cancer risk through high-resolution GED-ICP-MS and integrated ELCR analysis - Li-Ti Chou; Yi-Pin Lin; Chia-Hung Yu; Jun-Fa Ye; Wen-Che Hou; Ta-Chih Hsiao (Journal of Hazardous Materials, 2025)

Fabrication and application of ferrocene contained MOF derived porous carbon: A single multi-interference clean-up QuEChERS sorbent for facile analysis of triazine herbicides in various fruits and vegetables by LC-MS/MS - Zi-Ling Li; Da-Jin Yang; Jia-Qi Zhao; Wen-Jie Sun; Jie Gao; Shu-Feng Song; Hou-Jun Xu; Hai-Jie Li; Fa-Ming Tian; Man-Man Wang (Food Chemistry, 2025)

Molecular characterization and expression analysis of IL-21 and its four receptor genes in yellow catfish (Pelteobagrus fulvidraco) in response to Edwardsiella ictaluri infection - Zhang-Ping Li; Xin-Xin Jiang; Zi-Rui Tang; Mao-Mao Dong; Ping Jiang; Gui-Rong Zhang; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2025)

Glucose protects the pacific white shrimp Litopenaeus vannamei against Vibrio alginolyticus by inhibiting biofilm formation - Weibo Shi; Fa Dai; Ya Li; Zihao Sun; Min Meng; Qiuyan Yang; Weiwei Zhang (Fish & Shellfish Immunology, 2025)

Turning point of direct N2O emissions in China’s croplands dominated by reduced fertilizer usage since 2015 - Zimeng Li; Songbai Hong; Ziyuan Sun; Nan Cong; Yanzi Yan; Fa Li; Yuanyi Gao; Yan Sun; Yilin Chen; Yue Chen; Xuhui Wang; Shilong Piao (Agriculture, Ecosystems & Environment, 2025)

Sparse spike inversion with parity decomposition and stratal dip constraints - Jian-lei Zhang; Zhi-fang Ran; Fu-min Li; Guo-fa Li (Applied Geophysics, 2025)

Integrating synergistic effects of biodiversity conservation and ecosystem services into nature conservation strategies - Luu Van Thong Trac; Da-Li Lin; Chen-Fa Wu (Journal of Environmental Management, 2025)

Evaluation of the efficacy and safety of omega-3 fatty acid nutritional supplements from Schizochytrium sp. in dog food - Zi-Xu Zhang; Yan-Cheng Lin; Min Lian; Ying-Feng Li; Jin-Fa Chen; Xue-Lian Ma; Dong-Sheng Guo; Guang Yang; Xiao-Man Sun (Algal Research, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Mechanistic insights into endometriosis: roles of Streptococcus agalactiae and L-carnitine in lesion development and angiogenesis - Yuan Zhuang; Ting Lyu; Yang Chen; Wei Li; Lei Tang; Shi-ping Xian; Peng-fei Yang; Lijie Wang; Qian-qian Zhang; Chaoming Mei; Yu-jing Lin; Zhixiang Yan; et al. (Angiogenesis, 2025)

Seasonal and regional differences of heavy metals and nutrients from the five mariculture areas of large yellow croaker: Implications for environmental and fish quality - Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Jia-Lang Zheng; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Environmental Pollution, 2025)

Versatile Dual-Emissive Boron-Nitrogen Co-Doped carbon Dots: Unlocking efficient electroluminescent Light-Emitting diodes with breakthrough EQE Approaching 7% - Ming-Zhu Li; Hong-Ji Tan; Qi-Rui Liang; Jie-Rong Yu; Peng Huang; Xiao-Qi Lai; Chun-Fa Wen; Chun-Sing Lee; Qing-Xiao Tong; Jing-Xin Jian (Chemical Engineering Journal, 2025)

East Asian dust storm in March 2021: Perspective views from ground observation, satellite measurement and numerical simulation - Yi-Bo Xue; Xiao-Xiao Zhang; Jia-Qiang Lei; Sheng-Yu Li; Lian-You Liu; Zi-Fa Wang; Wen-Jun Tian; Xiao Tang; Xue-Shun Chen (Atmospheric Environment, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Helicobacter pylori VacA-induced gastric mucosal atrophy: a comparative analysis with other forms of atrophic gastritis - Yang-Kun Wang; Wen-Rui Chen; Ling-Yan Lu; Ying-Ying Li; Rui-Kun Qiu; Chao-Ya Zhu; Fa-Shun Zhang; Su-Nan Wang; Si-Liang Xu (Journal of Molecular Histology, 2025)

Shaking Table Testing and Numerical Simulation of Raft-Framed Structures Intersecting Tunnel Systems - Xiaogang Wei; Zhifan Qin; Shiao Wang; Shuaixin Ma; Mengqing Shi; Jingyu Fa; Shasha Lu; Guanghui Li (Geotechnical and Geological Engineering, 2025)

Deciphering the contribution of algae-rich microbial communities to dissolved organic matter in a eutrophic lake with distinct rainy and dry seasons - Han Yan; Hong-Fa Guo; Jia-Xun Li; Zhuo Chen; Shi-Qi Yin; Mo-Yu Shen; Yi Tao; Yin-Hu Wu; Hong-Ying Hu (Algal Research, 2025)

Vibrio splendidus virulence factor hop mediates coelomocytes apoptosis by interacting with HSC70 to promote JNK phosphorylation in Apostichopus japonicus - Yangxi Xiang; Weikang Liang; Fa Dai; Yina Shao; Si Zhu; Chenghua Li (Aquaculture, 2025)

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Differential crop yield responses to elevated CO2 attributed to varying biomass part stimulations: a meta-analysis - Yanling Bai; Liu Liu; Hao Li; Xi Peng; Keyu Fa; Guanhua Huang (Plant and Soil, 2025)

CTHRC1 expresses in cancer-associated fibroblasts and is associated with resistance to anti-androgen therapy in prostate cancer - Hai-qi Liang; Qi-huan He; Qiu-ju Wei; Qi-zhou Mo; Guang-lin Yang; Fa-ye Wei; Li-wei Wei; Yu-jian Li; Min Qin; Ji-wen Cheng (Genes & Genomics, 2025)

Mineralogy, geochemistry, and S isotope investigation of seafloor massive sulfides from the Yunzang hydrothermal field, South Atlantic Ridge - Wen-Sheng Li; Pei Ni; Xue-Fa Shi; Bing Li; Shao-Wen Liu; Stefano Albanese; Fei-Peng Fan; Guan-Hua Wang; An-Qi Hong (Journal of Geochemical Exploration, 2025)

Geochemical constraints on the link between lunar magma ocean cumulates and the source of Chang'E-5 basalts from olivine trace element abundances - Yong Wu; Jie-Jun Jing; Zi-Ying Li; Ming-Kuan Qin; Ben-Xun Su; Jun Zhong; Dong-Fa Guo; Guang Fan; Rui-Ping Liu; Sheng He; Ting Li; Xiang-Kun Ge; et al. (Icarus, 2025)

Dietary pyridoxine promoted muscle protein deposition relating to PI3K/AKT/TOR pathway and the ubiquitin proteasome system in grass carp (Ctenopharyngodon idella) - Li-Fu Gong; Xiao-Qiu Zhou; Lin Feng; Pei Wu; Wei-Dan Jiang; Yao-Bin Ma; Xiao-Wan Jin; Hong-Mei Ren; Jia-Yong Tang; Fa-Li Wu; Yang Liu (Food Bioscience, 2025)

Confining asymmetric water hydrogen-bond network to boost photoreduction of CO2 to formaldehyde - Minzhi Ma; Shuaikang Zhang; Mengge Jia; Tongqing Li; Jinshuo Chen; Shichu Zhao; Suxiang Ge; Zhi Zheng; Sixin Wu; Wenjun Fa (Chemical Engineering Journal, 2025)

Recurrence of Cerebral Arteriovenous Malformation Following Complete Obliteration Through Endovascular Embolization - Qiang Hao; Haibin Zhang; Heze Han; Hengwei Jin; Li Ma; Ruinan Li; Zhipeng Li; Anqi Li; Kexin Yuan; Qinghui Zhu; Ke Wang; Runting Li; et al. (Translational Stroke Research, 2025)

Magnitude, distribution and temporal trend of nitrous oxide emissions from China’s natural soils over 1980–2022 - Songbai Hong; Zimeng Li; Mingsong Tang; Fa Li; Yitong Yao; Yanzi Yan; Mingzhu He; Xuhui Wang; Hui Zeng; Shilong Piao (Science China Earth Sciences, 2025)

Nitrification inhibitor induced microbial NH4+-N immobilization improves maize nitrogen use efficiency in strong ammonia oxidation soil - Si-Yi Liu; Di Wu; Xiao-Tang Ju; Ju-Pei Shen; Yi Cheng; Na Deng; Xiao-Tong Song; Hong-Jie Di; Pei-Pei Li; Li-li Han; An-Hui Ge; Chuan-Fa Wu; et al. (Soil Biology and Biochemistry, 2025)

Exploring eutrophic effects of marine sediments underneath fish cage farms: Insights from changes in eukaryotic and bacterial communities and volatile organic compounds - Fa-Guo Wan; Yong-Long Chen; Jia-Lang Zheng; Wang-Yang Jin; Tian-Hong Chen; Qing-Ling Zhu; Qing-Hao Zhan; Li-Hua Jiang; Shun Chen; Wei-Hua Song; Xiao-Jun Yan (Science of The Total Environment, 2025)

Characterization of a stable QTL for quality-related traits and its effects on yields in wheat (Triticum aestivum L.) - Hongke Ding; Yankun Li; Jinlian Ou; Yuanze Song; Lihua Qiu; Xinyu Rong; Han Sun; Chunhua Zhao; Yongzhen Wu; Ran Qin; Jinlong Li; Cheng Liu; et al. (Theoretical and Applied Genetics, 2025)

Low-Frequency Sweep Design—A Case Study in Middle East Desert Environments - Yong-fei Qi; Zhou-hong Wei; Ming-tao Nie; Guo-fa Li; Tao Wang; Hai Ling; Sheng-kui Cong; Xin-yang Chen; Chang-ping Duan; Yang Liu (Applied Geophysics, 2025)

Land use change projection and driving factors exploration in Hainan Island based on the PLUS model - Jiahui Liu; Yaoqi Hou; Fangyi Li; Binbin Zheng; Zeheng Chen; Fa Zheng; Xiaohai Zhang; Rui Yu (Frontiers in Marine Science, 2025)
Introduction Land resources play a vital role in national economic and social development. Hainan Province faces the challenge of balancing land use with conservation while striving to develop a high-quality free trade port. This study aims to analyze land use changes and their driving factors to support sustainable land use policies. Methods This study utilised the GlobeLand30 dataset, along with data on temperature, precipitation, the digital elevation model (DEM), slope, soil, gross domestic product (GDP), and population, to apply the Patch-generating Land Use Simulation (PLUS) model. This model was used to analyse land use changes on Hainan Island from 2000 to 2020, to investigate the relationship between land use change and its driving factors. Results (1) During 2000~2020, forests and cultivated land were the predominant land use type, while wetlands and artificial surfaces increased by two times, and bare land remained stable; (2) Temperature significantly influenced cultivated land, forests, and grasslands, while GDP and population growth impacted water bodies and artificial surfaces; (3) The predicted land use map for 2020 achieved high accuracy (Kappa = 0.85); (4) By 2040, forests and cultivated land are expected to remain dominant, with grasslands and artificial surfaces decreasing, while wetlands and bare land are projected to increase. Discussion The study highlights the complex interactions between land use and its driving factors in Hainan. The findings provide valuable insights for sustainable land use policy development, balancing economic growth with ecological conservation in the region.

Corrigendum to “Maternal Zearalenone exposure impacted ovarian follicle formation and development of suckled offspring” [Sci. Total Environ. 788 (2021) 147792] - Li Kong; Ai-Hong Zhao; Qian-Wen Wang; Yan-Qin Feng; Zi-Hui Yan; Ming-Hao Li; Fa-Li Zhang; Han Wang; Kai-Yu Shen; Ying Liu; Yu-Jiang Sun; Wei Shen; et al. (Science of The Total Environment, 2025)

Importance of viewing angle: Hotspot effect improves the ability of satellites to track terrestrial photosynthesis - Haoran Liu; Jingfeng Xiao; Dalei Hao; Fa Li; Fujiang Ji; Min Chen (Remote Sensing of Environment, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Smartphone-based dual-mode aptasensor with bifunctional metal-organic frameworks as signal probes for ochratoxin A detection - Yu-Long Li; Yan-Yue Chen; Fa-Ting Xie; Qiu-Xia Li; Tong Yang; Yun-Hui Yang; Rong Hu (Food Chemistry, 2025)

Influence of the main controlling factors on the tangential restitution coefficient of rockfall impact - Zhong-Min Ji; Ting-Hui Wang; Jie Wu; Fa-Quan Wu; Zhen-Hua Li; Dong-Po Wang; Yi-Ju Tang; Chang-Le Zhao; Qing-He Niu (Engineering Geology, 2025)

The Role of SIRT1–BDNF Signaling Pathway in Fluoride-Induced Toxicity for Glial BV-2 Cells - Bo Yang; Feiqing Wang; Xu Yang; Xiaoshuang Yuan; Yuting Yang; Xiaoxu Chen; Tingting Tian; Fa Chen; Dongxin Tang; Zhixu He; Yang Liu; Yanju Li (Biological Trace Element Research, 2025)

Comparison of water quality, planktonic community, and volatile organic compounds in the seawater from five cage culture areas of large yellow croaker - Jia-Lang Zheng; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shang-Wei Xie; Li-Hua Jiang; Shun Chen; Qing-Ling Zhu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2025)

Comparative analysis of carotenoids, fatty acids, minerals, tastes, and odor in the skin of wild versus farmed large yellow croaker: Superior nutritional benefits with elevated heavy metal risks - Jia-Lang Zheng; Tao Zhu; Wang-Yang Jin; Qing-Hao Zhan; Fa-Guo Wan; Yong-Long Chen; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Shuang Chen; Wei-Ye Li; Yi-Fan Liu; et al. (Aquaculture, 2025)

Corrigendum to “Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis” [J Hazard Mater 468 (2024) 133836] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

The change rule of lipid oxidation and hydrolysis driven via water in Antarctic krill oil: Based on association colloid formation - Xue-Chen Pei; Xiang-Bo Zeng; De-Yang Li; Xin-Miao Wang; Fa-Wen Yin; Hui-Lin Liu; Da-Yong Zhou (Food Chemistry, 2025)

Research progress of electrospinning in food field: A review - Fa-Lin Sun; Ming-Yue Zhao; Yue Li; Zhi-Ying Li; Xiu-Jun Li; Nuo Wang; Bo-Wen Hu; Hao-Yu Xue; Min Zhao; Jin-Long Tian (Food Hydrocolloids, 2025)

A multirisk-rescued biomimetic nanozyme against periodontitis via inflammation targeting and microenvironment reprogramming - Lin Li; Rui-Xin Wu; Jia Wang; Rui Jin; Xin-Yu Zhang; Mei Xu; Si-Yao Li; Rui Gao; Bei-Min Tian; Xiao-Tao He; Fa-Ming Chen; Yuan Yin (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Effects of the types and ages of vegetation restoration on land surface roughness in the Eastern Hobq Desert, Northern China - Ji Feng; Yong-Sheng Wu; Li-Yuan Lu; Chasina Xi; Feng-Yan Wu; Chao-Yu Wang; Qiang Yin; Altantuya Dorjsuren; Rong-Liang Jia; Yu Qiao; Yuan-Fa Meng; Jie Yu (Science of The Total Environment, 2024)

Forms of rare earth loss and the function mechanism of acetic acid in the aluminum removal process of rare earth leaching liquor - Chen Xin; Chen Jin-fa; Xiao Xin-lei; Fan Lin; Xiao Yan-fei; Huang Li (Minerals Engineering, 2024)

A novel high-throughput quantitative method for the determination of per- and poly-fluoroalkyl substances in human plasma based on UHPLC-Q/Orbitrap HRMS coupled with isotope internal standard - Wenting Zhang; Qiuyan Lu; Huafeng Chen; Yuxiang Li; Yongyou Hua; Jing Wang; Fa Chen; Renjin Zheng (Journal of Hazardous Materials, 2024)

Ammonium mitigates cadmium toxicity by activating the bZIP20-APX2/CATA transcriptional module in rice seedlings in an ABA-dependent manner - Dong-Wei Di; Ting-Ting Li; Zheng-Lun Yu; Jie Cheng; Meng Wang; Chuan-Fa Liu; Yuan Wang; Herbert J. Kronzucker; Min Yu; Weiming Shi (Journal of Hazardous Materials, 2024)

In-situ and ex-situ selective catalysis of biochar-based catalysts for the production of high-quality bio-oil and H2-rich gas from tobacco stem - Xin Tang; Xiang Yang Li; Qiu Fa He; Yao Peng; Bin Peng; Yu Zhang; Wei Luo; Zhi Zhou (Journal of Environmental Chemical Engineering, 2024)

Long-term effects including shrinkage and interfacial creep on bond behavior of concrete-filled steel tubes (CFST): Experiment and design - Bo Li; Wen-Qi Xie; Fa-Cheng Wang (Engineering Structures, 2024)

Polyoxometalate oxate solution: An electrolyte additive to sustainably improve the anodes electrode of aqueous Zn ion batteries - Li-li Du; Zhuo Li; Wei-jia Song; Qing-peng Bao; Peng-fei Wang; Zhe Gong; Yu-hang Zhang; Yu-han Wu; Fa-nian Shi; Ming-dong Zhou; Kai Zhu (Chemical Engineering Journal, 2024)

Permafrost impacts on chemical weathering and CO2 budgets in the Tibetan Plateau: Micro-watershed perspective on a headwater catchment - Zhou Huiling; Li Zongxing; Yu Zhengliang; Wang Yunying; Du Fa; Xue Jian (CATENA, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Mechanism of discoloration of Antarctic krill oil upon storage: A study based on model systems - Xiang-Bo Zeng; Xue-Chen Pei; De-Yang Li; Fa-Wen Yin; Hui-Lin Liu; Meng-Ling Jin; Jiang-Hua Zhang; Da-Yong Zhou (Food Chemistry, 2024)

Optimisation of extraction performance for uranium with covalent organic frameworks of β-ketoenamines with different functional groups - Jihe Zhao; Quan Cao; Lei Zhao; Fengwe Li; yangyang xin; Yanli Liu; Wansheng Zhang; Xiaolin shi; Meiyan Wu; Yongye Zhao; Yun Fa; Huizhou Liu (Chemical Engineering Journal, 2024)

Skeleton design engineering of covalent organic frameworks to enable in situ incorporation of coordination sites for improved extraction of uranyl ions - Jihe Zhao; Lei Zhao; Quan Cao; Guangying Fu; Fengwe Li; Huizhou Liu; Yun Fa (Chemical Engineering Journal, 2024)

Yr29 combined with QYr.nwafu-4BL.3 confers durable resistance to stripe rust in wheat cultivar Jing 411 - Mingjie Xiang; Bo Tian; Jianghao Cao; Shengjie Liu; Caie Zhou; Xiaoting Wang; Yibo Zhang; Jiale Li; Xunying Yuan; Jufen Wan; Rui Yu; Weijun Zheng; et al. (Theoretical and Applied Genetics, 2024)

Comparative study on the quality of wild and ecologically farmed large yellow croaker through on-site synchronous sampling from the Nanji Archipelago in the East China Sea - Jia-Lang Zheng; Yong-Long Chen; Fa-Guo Wan; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Ling Zhu; Li-Hua Jiang; Wei-Ye Li; Wen-Tao Ye; Yi-Fan Liu; Wei-Hua Song; et al. (Aquaculture, 2024)

The resistance mechanism of humic acids and proteins in soluble microbial products from activated sludge against silver nanoparticles - Jia Kang; Yi-hang Wang; Yao-wen Zhang; Chu-qiong Song; Ao-di Wang; Ning Zhou; Yi-hui Zhang; Fa-zhan Li; Shu-li Liu; Li-sha Liu; Gang-fu Song; Bai-hong Wang (Journal of Environmental Chemical Engineering, 2024)

Calreticulin from Apostichopus japonicus relieves endoplasmic reticulum stress induced by Vibrio splendidus through autophagy - Weikang Liang; Lincheng Hu; Fa Dai; Yue Shi; Lei Yang; Chenghua Li (Fish & Shellfish Immunology, 2024)

Corrigendum to “Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig” [Environ. Pollut. 329 (2023) 121729] - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2024)

Overlapping hotspot tracks and melts from diffuse plume materials in the upper mantle generated intraplate seamount groups in the West Pacific - Xun Wei; Guo-Liang Zhang; Ji Zhang; Xue-Fa Shi; Paterno R. Castillo; Yan Zhang; Wan-Feng Zhang; Yi-Gang Xu; Hong-Yan Li; Hui Zhang (Earth and Planetary Science Letters, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

EMS-induced missense mutation in TaCHLI-7D affects leaf color and yield-related traits in wheat - Zixu Wang; Huiyuan Xu; Faxiang Wang; Lingling Sun; Xiangrui Meng; Zhuochun Li; Chang Xie; Huijiao Jiang; Guangshuo Ding; Xinrong Hu; Yuhang Gao; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Sodium Fluoride Exposure Induces Developmental Toxicity and Cardiotoxicity in Zebrafish Embryos - Feiqing Wang; Fa Chen; Wen Song; Yanju Li; Haiyan Wu; Tingting Tian; Mengxian Tian; Dongxin Tang; Yang Liu (Biological Trace Element Research, 2024)

Comparative study on the morphological characteristics, nutritional quality, and tastes of large yellow croaker from five cage culture areas: Relay farming improved fish quality - Jia-Lang Zheng; Fa-Guo Wan; Yong-Long Chen; Li-Hua Jiang; Qing-Hao Zhan; Tian-Hong Chen; Shun Chen; Qing-Lin Zhu; Wei-Ye Li; Yi-Fan Liu; Wei-Hua Song; Xiao-Jun Yan (Aquaculture, 2024)

Self-hydrogen transfer hydrogenolysis of β-O-4 bonds in lignin model compounds over NiCu/Al2O3 catalyst - Fa-Peng Wu; Le-Le Qiu; Yun-Peng Zhao; Zong-Pin Fu; Jing Liang; Jian Xiao; Jian Li; Fang-Jing Liu; Jing-Pei Cao (Fuel, 2024)

Highly stable planted MXene auxiliary layer for high-performance zinc anode deposition regulation - Qing-peng Bao; Zhuo Li; Bin-bin Sui; Huan Liu; Peng-fei Wang; Zhe Gong; Yu-hang Zhang; Yu-han Wu; Fa-nian Shi; Ming-dong Zhou; Kai Zhu (Chemical Engineering Journal, 2024)

SA-DNA hydrogel microspheres for Ultra-Selective uranyl (VI) extraction from seawater - Wansheng Zhang; Yangyang Xin; Yun Fa; Fei Li; Yanli Liu; Mengqin Wu; Jihe Zhao; Hongwei Xu; Huizhou Liu (Chemical Engineering Journal, 2024)

Failure Mechanism and Active Support of Large-Span Tunnel with Unstable Rock Blocks: A Case Study - Wen-xu Li; Zhi-chao Xue; Le-min Liu; Shuo Zhang; Fu-yong Zhang; Wei-teng Li; Xin-jie Man; Xing Shao; Ming-fa Wang; Chang-an Zhang (Geotechnical and Geological Engineering, 2024)

N-th root slant stack for enhancing weak seismic signals - Fei Li; Jun-fa Xie; Zong-hui Yao; Mei Li; Yu-lian Zhao; Wei-ming Liu; Juan Chen (Applied Geophysics, 2024)

How to identify public risk perception in public health emergencies and explore its driving mechanism? An empirical analysis in the Xi'an epidemic - Yueqian Zhang; Xinchun Li; Quanlong Liu; Zunxiang Qiu; Ziwei Fa (Sustainable Cities and Society, 2024)

Origin and evolution of a porphyry-skarn-stratabound system: constraints from geology, magmatic-hydrothermal zircon U–Pb and molybdenite Re–Os geochronology, and in situ S isotopes of the Dongguashan Cu(–Au) deposit, eastern China - Ke Chen; Yong-Jun Shao; Zhong-Fa Liu; Jun-Ke Zhang; Yong-Shun Li; Yu-Ce Zhang; Yuan-Dong Zhan (Gondwana Research, 2024)

CA1 Modulates the Osteogenic Differentiation of Dental Follicle Stem Cells by Activating the BMP Signaling Pathway In Vitro - Jin-ze Zhao; Ying-Ying Ge; Ling-fa Xue; Yao-xiang Xu; Jin Yue; Cong Li; Wen-lin Xiao (Tissue Engineering and Regenerative Medicine, 2024)

Characterizing the distribution pattern of traffic-related air pollutants in near-road neighborhoods - Meng-Yi Jin; John Gallagher; Xiao-Bing Li; Kai-Fa Lu; Zhong-Ren Peng; Hong-Di He (Environmental Monitoring and Assessment, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Molecular characterization, expression analysis and function identification of Pf_IL-12p35, Pf_IL-23p19 and Pf_IL-12p40 genes in yellow catfish (Pelteobagrus fulvidraco) - Xin-Xin Jiang; Zi-Rui Tang; Zhang-Ping Li; Gui-Rong Zhang; Xu Zhou; Xu-Fa Ma; Kai-Jian Wei (Fish & Shellfish Immunology, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Early Eocene marine microgastropods from the Zhupure Formation in Yadong, Southern Tibet, China - Xin-Fa Li; Guo-Biao Li; Christopher L. Garvie (Palaeoworld, 2024)

Early Triassic high-K granitoids and enclaves of the Daheba pluton, West Qinling (China): Implications for relative contributions of crust and mantle - Feng-Hui Zou; M. Santosh; Chang-Qian Ma; Cai-Lai Wu; Jian-Ping Zheng; Fa-Bin Pan; Han-Ming Gu; Li-Huan Deng (Journal of Asian Earth Sciences, 2024)

Mechanism of color change in Antarctic krill oil during storage - Xiang-Bo Zeng; Fa-Wen Yin; Guan-Hua Zhao; Chao Guo; De-Yang Li; Hui-Lin Liu; Lei Qin; Fereidoon Shahidi; Da-Yong Zhou (Food Chemistry, 2024)

A portable magnetic electrochemical sensor for highly efficient Pb(II) detection based on bimetal composites from Fe-on-Co-MOF - Yijiao Zhang; Siwei Jin; Renlong Liu; Zuohua Liu; Li Gong; Li Zhang; Tengda Zhao; Wei Yin; Shiqi Chen; Huanbao Fa; Lidan Niu (Environmental Research, 2024)

RETRACTED: Vegetation restoration strategies based on plant water use patterns - Juan Gui; Zongxing Li; Fa Du; Xiaoyin Liu; Jian Xue (Science of The Total Environment, 2024)

Co-pyrolysis of saw dust and oily sludge with waste-heat utilization of steel slag on rotary kiln simulated engineering practice - Hongdi Yu; Fawei Lin; Xuan Guo; Hongyun Yao; Fa Zheng; Jiantao Li; Meng Zhang; Rundong Li; Beibei Yan; Guanyi Chen (Fuel, 2024)

Influences of removable gas injection methods on the temperature field and gas composition of the underground coal gasification process - Fa-qiang Su; Jun-nan Yang; Xiao-long He; Meng-jia Dai; Akihiro Hamanaka; Yi- he Yu; Wen Li; Jiao-yuan Li (Fuel, 2024)

Who are root hazards? A research on optimization of safety training management in coal mine enterprises from data-driven perspective - Ziwei Fa; Ke Yan; Zunxiang Qiu; Yueqian Zhang; Quanlong Liu; Xinchun Li (Resources Policy, 2024)

Bacillus licheniformis ameliorates Aflatoxin B1-induced testicular damage by improving the gut-metabolism-testis axis - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Yu-Mei Chen Yan; Yu Chen; Guo-Ming Yang; Wei Shen; Xi-Feng Zhang (Journal of Hazardous Materials, 2024)

Corrigendum to “Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis” [J Hazard Mater 459 (2023) 132226] - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2024)

The effect of freeze-thaw action on the dynamic change of supra-permafrost water sources: A stable isotope perspective - Juan Gui; Zongxing Li; Jian Xue; Fa Du; Qiao Cui (Journal of Environmental Management, 2024)

Auto-mmBCFAs: A swift precision approach for determination of monomethyl branched-chain fatty acids - Yuan He; Jie Li; Jia-Chen Shi; Yuan-Fa Liu; Yong-Jiang Xu (Food Bioscience, 2024)

Windows of sensitivity for risk of adverse birth outcomes related to gestational PM2.5 exposure: Evidence from a natural experiment - Wei Ni; Yuhan Xing; Guoju Li; Zhanhui Du; Ping Yang; Qinzheng Wang; Xinmeng Yang; Bei Lyu; Hongge Fa; Qiuling Shi; Quansheng Xing (Environmental Pollution, 2024)

Quantitative trait loci detection for three tiller-related traits and the effects on wheat (Triticum aestivum L.) yields - Yibiao Cai; Xiaohan Zhou; Chenyang Wang; Aifeng Liu; Zhencang Sun; Shihui Li; Xinyao Shi; Shuang Yang; Yuxiang Guan; Jiajia Cheng; Yongzhen Wu; Ran Qin; et al. (Theoretical and Applied Genetics, 2024)

Numerical simulation analysis of debris filtration in the bottom nozzle - Shuang Deng; Quan-yao Ren; Jing Zhang; Xin Duan; Fa-wen Zhu; Yong Xin; Xin-Yu Yang; Quan Li; Ying-wei Wu (Annals of Nuclear Energy, 2024)

Examination of the effects of triacylglycerol lipase on astaxanthin conversion in the black tiger prawn Penaeus monodon - Xin-Tao Li; Li-Shi Yang; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Fa-Lin Zhou; Yun-Dong Li; Jian-Zhi Shi; Xu Chen; Yu-kai Yang; Jian-Hua Huang (Aquaculture, 2024)

Design and analysis of a novel oscillating flow generator connected to an offshore wind turbine tower - Wei Jun Zhu; Shu Qing Zhuang; Zhen Ye Sun; Ye Li; Jiu Fa Cao; Wen Zhong Shen (Ocean Engineering, 2024)

Fine mapping of a major QTL, qKl-1BL controlling kernel length in common wheat - Ran Qin; Mingsu Cao; Jizi Dong; Linqu Chen; Haoru Guo; Qingjie Guo; Yibiao Cai; Lei Han; Zhenjie Huang; Ninghao Xu; Aoyu Yang; Huiyuan Xu; et al. (Theoretical and Applied Genetics, 2024)

Correction to: Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2024)

Optimization of ultrasound-assisted extraction of glycyrrhizic acid and glabridin from Glycyrrhiza glabra L. using response surface methodology and development of a green analytical method - Ye-fei Liang; Qing Wen; Zhen-fei Yang; Cui-qin Li; Fa-rong Li (Sustainable Chemistry and Pharmacy, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

Confined bismuth single atoms and nanoparticles dual-sites constructed via reverse etching for CO2 photoreduction to CH4 - Dou Zhang; Ying-jie Sun; Kai-hua Zhang; Guang Yang; Xiao-jing Wang; Yi-lei Li; Hui-yun Han; Xinying Liu; Bao-Hang Han; Fa-tang Li (Chemical Engineering Journal, 2024)

3D network of zinc powder woven into fibre filaments for dendrite-free zinc battery anodes - Lin Sha; Bin-Bin Sui; Peng-Fei Wang; Zhe Gong; Yu-Hang Zhang; Yu-Han Wu; Li-Na Zhao; Jun-Jie Tang; Fa-Nian Shi (Chemical Engineering Journal, 2024)

Effects of Brown Fishmeal on Growth Performance, Digestibility, and Lipid Metabolism of the Chinese Soft-Shelled Turtle (Pelodiscus sinensis) - Guo-Fang Zhong; Liang-Fa Zhang; Yi Zhuang; Qi Li; He Huang; Cong Cao; Zhan-Ying Zhu; Zhong-Yuan Huang; Nu-An Wang; Kun Yuan (Marine Biotechnology, 2024)

Global impacts of vegetation clumping on regulating land surface heat fluxes - Fa Li; Dalei Hao; Qing Zhu; Kunxiaojia Yuan; Renato K. Braghiere; Liming He; Xiangzhong Luo; Shanshan Wei; William J. Riley; Yelu Zeng; Min Chen (Agricultural and Forest Meteorology, 2024)

The remediation potential and kinetics of Pb2+ adsorbed by the organic frameworks of Cladophora rupestris - Lu-sheng Zhang; Xiao-yu Feng; Chang-fa Qiu; Ling-sheng Li; Yu Sun; Xin-yi Tao; Xin-yue Li; Zhao-wen Liu; De-ju Cao (Environmental Science and Pollution Research, 2024)

Effective degradation of zearalenone by dye-decolorizing peroxidases from Pleurotus ostreatus and its metabolic pathway and toxicity analysis - Shuai Ding; Chen Lin; Qiuyun Xiao; Fa Feng; Junfeng Wang; Xing Zhang; Shengjing Yang; Lingling Li; Fei Li (Science of The Total Environment, 2024)

Enhancing flame retardancy, mechanical durability, and anti-aging property of polyurethane foam via novel cyclic phosphonate - Zhi-Cheng Fu; Fa-Yang Bu; Zhe-Peng Li; Ting Wang; Jin-Ni Deng; Hai-Bo Zhao; Sheng-Chao Huang; Yu-Zhong Wang; Ming-Jun Chen (Chemical Engineering Journal, 2024)

Active/passive protection and anti-UV waterborne epoxy coatings based on low defect functionalized PDA-GO-CeO2 material for excellent corrosion control - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Hao-Jie Yan; Hui-Song Hu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2024)

Chiral Au nanostars for SERS sensing of enantiomers discrimination, multibacteria recognition and photothermal antibacterial application - Xueqin Huang; Qiuxia Chen; Yiling Ma; Chan Huang; Weixia Zhi; Jiahao Li; Runmin Zeng; Jiang Pi; Jun-fa Xu; Jun Xu; Wanyong Yang; Jianglin Zhang; et al. (Chemical Engineering Journal, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Induced differentiation of primordial germ cell like cells from SOX9+ porcine skin derived stem cells - Geng Zhang; Xin-Xiang Xie; Shu-Er Zhang; Fa-Li Zhang; Chun-Xiao Li; Tian Qiao; Paul W. Dyce; Xin-Lei Feng; Wei-Bo Lin; Qi-Cheng Sun; Wei Shen; Shun-Feng Cheng (Theriogenology, 2023)

Occurrence of liquid crystal monomers in indoor and outdoor air particle matters (PM10): Implications for human exposure indoors - Li-Li Yao; Jun-Li Wang; Rong-Fa Xu; Ming Zhu; Yan Ma; Bin Tang; Qi-Yuan Lu; Feng-Shan Cai; Xiao Yan; Jing Zheng; Yun-Jiang Yu (Science of The Total Environment, 2023)

Eudesmane-type sesquiterpenoids from the aerial parts of Artemisia lavandulaefolia and their anti-pancreatic cancer activities - Lin-Fen Ding; Guo-Xian Hu; Yu-Yao Liu; Qiu-Hua Wang; Zhang-Juan Li; Meng-Xia Shen; Gui-Fa Zhu; Xing-De Wu; Jia Su (Phytochemistry, 2023)

Underwater glider trajectory control based on virtual hinges of multi-body model - Shuai Li; Yanhui Wang; Muhua Ren; Wendong Niu; Ming Yang; Shaoqiong Yang; Xuehao Wang; Shuai Fa (Ocean Engineering, 2023)

Exploring the antioxidant “cut-off effect” of gallic acid alkyl esters in dried oysters (Crassostrea gigas) during storage - Guan-Hua Zhao; Ying Luo; Qi Li; Min Zhang; Fa-Wen Yin; Da-Yong Zhou (Food Bioscience, 2023)

C4 leaf development and evolution - Chi-Fa Huang; Wen-Yu Liu; Chun-Ping Yu; Shu-Hsing Wu; Maurice S.B. Ku; Wen-Hsiung Li (Current Opinion in Plant Biology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Fast perception of rock mass strength and integrity in TBM tunnelling using in-situ penetration test - Wei-Qiang Xie; Xiao-Ping Zhang; Shao-Hui Tang; Xiao-Li Liu; Xin-Fang Li; Qi Zhang; Fa-Yuan Yan; Chen Xu; Quan-Sheng Liu (Tunnelling and Underground Space Technology, 2023)

A marine coating: Self-healing, stable release of Cu2+, anti-biofouling - Liuqin Zhang; Huali Li; Xiaohu Zhang; Qiuping Li; Guangyu Zhu; Fa-Qian Liu (Marine Pollution Bulletin, 2023)

ID3 regulates progesterone synthesis in bovine cumulus cells through modulation of mitochondrial function - Zi-Bin Liu; Jia-Bao Zhang; Sheng-Peng Li; Wen-Jie Yu; Na Pei; Hai-Tao Jia; Ze Li; Wen-Fa Lv; Jun Wang; Nam-Hyung Kim; Bao Yuan; Hao Jiang (Theriogenology, 2023)

Four previously undescribed diketopiperazines from marine fungus Aspergillus puniceus FAHY0085 and their effects on liver X receptor α - Qi Hong; Miao-Miao Guo; Jin Yang; Xing Wei; Li Liao; Xiu-Juan Xin; Di Zhang; Fa-Liang An (Phytochemistry, 2023)

New nornemoralisin and nemoralisin diterpenoids from Aphanamixis polystachya - Yan-Wu Chen; Shi-Li Wu; Fa-Wu Dong; Hua-Yi Jiang; Hong-Ping He (Phytochemistry Letters, 2023)

Cross-species analysis of transcriptome emphasizes a critical role of TNF-α in mediating MAP2K7/AKT2 signaling in zearalenone-induced apoptosis - Fa-Li Zhang; Ke-Xin Zhu; Jing-Ya Wang; Min Zhang; Jia-Mao Yan; Qing-Chun Liu; Xiao-Yuan Zhang; Jia-Chen Guo; Xuan Liu; Qi-Cheng Sun; Wei Ge; Lan Li; et al. (Journal of Hazardous Materials, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Characterization and fine mapping analysis of a major stable QTL qKnps-4A for kernel number per spike in wheat - Ran Qin; Tianhang Ma; Yibiao Cai; Xinyao Shi; Jiajia Cheng; Jizi Dong; Chenyang Wang; Shihui Li; Guoqing Pan; Yuxiang Guan; Lei Zhang; Shuang Yang; et al. (Theoretical and Applied Genetics, 2023)

Particularity of hydrological processes under heavy ablation based on environmental isotopes in transition zones between endorheic and exorheic basins - Juan Gui; Zongxing Li; Baijuan Zhang; Jian Xue; Fa Du; Lanping Si (Journal of Environmental Management, 2023)

Scheme-II heterojunction of Bi2WO6@Br-COFs hybrid materials for CO2 photocatalytic reduction - You Wang; Zhongke Dai; Jiajia Wang; Du Zhang; Fa Zhou; Jiawei Li; Jianhan Huang (Chemical Engineering Journal, 2023)

High-efficient electromagnetic wave absorption of coral-like Co/CoO/RGO hybrid aerogels with good hydrophobic and thermal insulation properties - Yuan Shu; Tingkai Zhao; Jalil abdul; Xianghong Li; Lei Yang; Fa Luo (Chemical Engineering Journal, 2023)

In vivo antibacterial activity of medicinal plant Sophora flavescens against Streptococcus agalactiae infection - Fa‐Li Zhang; Liu Yang; Wei‐Hao He; Ling‐Jun Xie; Fei Yang; Ying‐Hui Wang; Ai‐Guo Huang (Journal of Fish Diseases, 2023)
Streptococcosis disease caused by Streptococcus agalactiae (Group B Streptococcus, GBS) results in a huge economic loss of tilapia culture. It is urgent to find new antimicrobial agents against streptococcosis. In this study, 20 medicinal plants were evaluated in vitro and in vivo to obtain medicinal plants and potential bioactive compounds against GBS infection. The results showed that the ethanol extracts of 20 medicinal plants had low or no antibacterial properties in vitro, with a minimal inhibitory concentration ≥256 mg/L. Interestingly, in vivo tests showed that 7 medicinal plants could significantly inhibit GBS infection in tilapia, and Sophora flavescens (SF) had the strongest anti‐GBS activity in tilapia, reaching 92.68%. SF could significantly reduce the bacterial loads of GBS in different tissues (liver, spleen and brain) of tilapia after treated with different tested concentrations (12.5, 25.0, 50.0 and 100.0 mg/kg) for 24 h. Moreover, 50 mg/kg SF could significantly improve the survival rate of GBS‐infected tilapia by inhibiting GBS replication. Furthermore, the expression of antioxidant gene cat , immune‐related gene c‐type lysozyme and anti‐inflammatory cytokine il‐10 in liver tissue of GBS‐infected tilapia significantly increased after treated with SF for 24 h. Meanwhile, SF significantly reduced the expression of immune‐related gene myd88 and pro‐inflammatory cytokines il‐8 and il‐1β in liver tissue of GBS‐infected tilapia. The negative and positive models of UPLC‐QE‐MS, respectively, identified 27 and 57 components of SF. The major components of SF extract in the negative model were α, α‐trehalose, DL‐malic acid, D‐ (−)‐fructose and xanthohumol, while in the positive model were oxymatrine, formononetin, (−)‐maackiain and xanthohumol. Interestingly, oxymatrine and xanthohumol could significantly inhibit GBS infection in tilapia. Taken together, these results suggest that SF can inhibit GBS infection in tilapia, and it has potential for the development of anti‐GBS agents.

Cinnamigones A–C, three highly oxidized guaiane-type sesquiterpenes with neuroprotective activity from Cinnamomum migao - Lang Zhou; Li-shou Yang; Li Wang; Hua-dan Liu; Ming Gao; Fa-ju Chen; Juan Yang; Qi-ji Li; Xiao-sheng Yang (Phytochemistry, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Quantifying traffic-related carbon emissions on elevated roads through on-road measurements - Dan-Ni Lu; Hong-Di He; Hong-Mei Zhao; Kai-Fa Lu; Zhong-Ren Peng; Jian Li (Environmental Research, 2023)

Influence of Evaporating Under the Clouds on the Precipitation Stable Isotope in the Transition Zone Between Tibetan Plateau and Arid Region of China - Juan Gui; Zongxing Li; Fa Du; Baijuan Zhang; Jian Xue; Qiao Cui (Chinese Geographical Science, 2023)

Aflatoxin B1 disrupts testicular development via the cell cycle-related Ras/PI3K/Akt signaling in mice and pig - Fa-Li Zhang; Hao-Hai Ma; Pei-Yu Dong; Zheng-Ning Yuan; Shu-Er Zhang; Ai-Hong Zhao; Huan-Qi Liu; Massimo De Felici; Wei Shen; Xi-Feng Zhang (Environmental Pollution, 2023)

Hydrologic connectivity between water in permafrost active layer and river water in a small alpine catchment in the northeastern Tibetan Plateau - Zongxing Li; Huiling Zhou; Baijuan Zhang; Du Fa; Jian Xue (Applied Geochemistry, 2023)

A green synthesized medicine residue carbon-based iron composite for the removal of chromium (VI) and cadmium (II): Performance, kinetics and mechanism - Fa-Ming Diao; Man-Li Chen; Lin-Yin Tong; Ying-Nan Chen; Zeng-Hui Diao (Environmental Science and Pollution Research, 2023)

An integrated strategy combining network toxicology and feature-based molecular networking for exploring hepatotoxic constituents and mechanism of Epimedii Folium-induced hepatotoxicity in vitro - Zhen Zhao; Jin-Fa Du; Qiao-Lei Wang; Fang-Ning Qiu; Xu-Yan Chen; Feng-Jie Liu; Ping Li; Yan Jiang; Hui-Jun Li (Food and Chemical Toxicology, 2023)

Barium(II)-based semiconductive coordination polymers for high-performance direct X-ray detection and imaging: Reducing the exciton binding energy via enhancing π-π interactions - Mei-Juan Xie; Jian Lu; Bao-Yi Li; Wen-Fei Wang; Shuai-Hua Wang; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2023)

A novel cerium organic network modified graphene oxide prepared multifunctional waterborne epoxy-based coating with excellent mechanical and passive/active anti-corrosion properties - Hao Li; Qin-Hao Zhang; Xian-Ze Meng; Pan Liu; Lian-Kui Wu; Fa-He Cao (Chemical Engineering Journal, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

LC-MS Based Metabolomic Profiling of Largehead Hairtail (Trichiurus japonicus) Ovary Reveals Metabolic Signatures of Ovarian Developmental Process (II–IV) - Liu-Ying Feng; Li-Ping Yan; Run-Wei Li; Sheng-Fa Li; Jia-Hua Cheng; Yan Jin (Fishes, 2023)
Trichiurus japonicus is an economically important fish that ranks 11th in global marine fish capture production. However, the reproductive characteristics of this fish have undergone notable changes in recent decades, potentially affecting the quality of offspring and sustainable utilization. To improve our understanding of the physiological regulation of maturation in T. japonicus, untargeted liquid chromatography mass spectrometry was utilized to identify the small molecules that characterize the comprehensive metabolic profiles of ovaries during ovary development from stage II to stage IV. According to the results of OPLS-DA, the ovarian metabolite profiles of the three developmental stages were separated. The concentrations of 124 and 100 metabolites were significantly altered between stage II vs. III and III vs. IV, respectively. Lipids and lipid-like molecules accounted for the largest proportion of the altered metabolites, followed by amino acids, peptides, and analogues. The significantly altered metabolites-enriched pathways differed slightly between stages II and III and stages III and IV. Steroid-related pathways were heavily affected during stages II to III, while significantly altered metabolites from stages III to IV were involved in oocyte-maturation-related pathways. Through metabonomics analysis, potentially important metabolic pathways and metabolites between different ovarian stages were detected, providing basic information for further investigation of maturation mechanisms in wild fish.

Adverse impacts of development on the deltamethrin-exposed host Ephestia elutella (Lepidoptera: Pyralidae) on population parameters of Habrobracon hebetor (Hymenoptera: Braconidae) - Xiu-Qin Wang; Hou-Ding Ou; Hao-Xi Li; Lan Wei; Yao Huang; Mao-Fa Yang (Crop Protection, 2023)

Isoquinoline alkaloids from Corydalis edulis Maxim. Exhibiting insulinotropic action - Zhi-Tian Peng; Hui-Xia Huo; Ling-Hui Chao; Yue-Lin Song; Di-Fa Liu; Zhang-Wei Wang; Yuan Zhang; Yun-Fang Zhao; Peng-Fei Tu; Jiao Zheng; Jun Li (Phytochemistry, 2023)

Trace element geochemistry, oxygen isotope and U–Pb geochronology of multistage scheelite: Implications for W-mineralization and fluid evolution of Shizhuyuan W–Sn deposit, South China - Kun-Yan Wu; Biao Liu; Qian-Hong Wu; She-Fa Chen; Hua Kong; Huan Li; Safiyanu Muhammad Elatikpo (Journal of Geochemical Exploration, 2023)

Glyphosate-induced autophagy inhibition results in hepatic steatosis via mediating epigenetic reprogramming of PPARα in roosters - Cai-Yu Lian; Sheng Wei; Zi-Fa Li; Shu-Hui Zhang; Zhen-Yong Wang; Lin Wang (Environmental Pollution, 2023)

Stochastic-based approach to quantify the uncertainty of groundwater vulnerability - Chuen-Fa Ni; Tien-Duc Vu; Wei-Ci Li; Minh-Tuan Tran; Van-Cuong Bui; Minh-Hoang Truong (Stochastic Environmental Research and Risk Assessment, 2023)

Elevated Interleukin-37 Associated with Dengue Viral Load in Patients with Dengue Fever - Jun-Ai Zhang; Jia-Jun Wang; Wen-Ting Zhang; Li Zhang; Bi-Ying Zheng; Gan-Bin Liu; Jing Liang; Yuan-Bin Lu; Xian-Jin Wu; Shu-Ying Yao; Guo-Ying Chen; Yun-Qi Xie; et al. (Current Microbiology, 2023)
Dengue remains a public health issue worldwide. Similar to chronic infectious diseases, stimulation of cytokine production is not enough to drive immune effector cells for effective virus clearance. One possible mechanism is the virus induces a large number of negative stimulatory cytokines inhibiting immune response. Interleukin 37 (IL-37) plays a crucial regulatory role in infection and immunity, inhibits innate and adaptive immunity as an anti-inflammatory cytokine by inhibiting proinflammatory mediators and pathways. To date, there are few studies reporting correlations between dengue fever (DF) and IL-37. In this study we found that the serum IL-37b and IL-37b-producing monocytes in patients were significantly increased in DF patients. A majority of the IL-37b produced by DF patients was produced by monocytes, not lymphocytes. Increased levels of IL-6, IL-10, and IFN-α were also found in DF patients. However, we failed to detect IL-1β, IL-17A and TNF-α in plasma, because of off-target. In our study, there was no relation between IL-6, IL-10, and IFN-α expressions and IL-37b in serum ( P > 0.05). The IL-37b-producing monocytes were negatively correlated with the level of IFN-α in serum and platelet count, and positively correlated with lymphocytes percentage ( P < 0.05, respectively). Additionally, serum DENV nonstructural protein 1 levels were positively correlated with monocytes percentages ( P < 0.05). Our data represents findings for IL-37b expression and its potential mechanisms in DF patients’ immune response.

Vapor-deposited digenite in Chang’e-5 lunar soil - Zhuang Guo; Chen Li; Yang Li; Yanxue Wu; Chenxi Zhu; Yuanyun Wen; Wenzhe Fa; Xiongyao Li; Jianzhong Liu; Ziyuan Ouyang (Science Bulletin, 2023)

Cooling rate of clinopyroxene reveals the thickness and effusion volume of Chang'E-5 basaltic flow units - Zilong Wang; Wei-(RZ) Wang; Wei Tian; Huijuan Li; Yuqi Qian; Junling Pei; Zhenyu Chen; Dianbing Wang; Ping-Ping Liu; Wenzhe Fa; Jiang Wu; Hong Bao (Icarus, 2023)

In-situ growth of carbon nanotubes for improving the performance of Co-N/C catalysts in proton exchange membrane fuel cell - Xi-Ming Qu; Shu-Hu Yin; Ya-Ni Yan; Jian Yang; Yan-Rong Li; Xiao-Yang Cheng; Fa Lu; Chong-Tai Wang; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2023)

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

Anisotropic creep behavior of soft-hard interbedded rock masses based on 3D printing and digital imaging correlation technology - Yun Tian; Fa-quan Wu; Hong-ming Tian; Zhe Li; Xiao-yun Shu; Lin-kai He; Man Huang; Wei-zhong Chen (Journal of Mountain Science, 2023)

Regional differences in gully network connectivity based on graph theory: a case study on the Loess Plateau, China - Jian-hua Cheng; Lan-hua Luo; Fa-yuan Li; Lu-lu Liu; Ling-zhou Cui (Journal of Mountain Science, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Melamine-functionalization of the carbonyl-rich polymers for iodine vapor and Hg2+ capture - Du Zhang; Yiping Chen; Jiajia Wang; You Wang; Yiwen Cao; Jiawei Li; Fa Zhou; Jianhan Huang; You-Nian Liu (Chemical Engineering Journal, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Assessment and prevention on the potential rockfall hazard of high-steep rock slope: a case study of Zhongyuntai mountain in Lianyungang, China - Zhong-Min Ji; Tian-Li Chen; Fa-Quan Wu; Zhen-Hua Li; Qing-He Niu; Ke-Yi Wang (Natural Hazards, 2023)

Pyrite trace element and S-Pb isotopic evidence for contrasting sources of metals and ligands during superimposed hydrothermal events in the Dongping gold deposit, North China - Huan Li; Da-Peng Zhu; Thomas J. Algeo; Ming Li; Wei-Cheng Jiang; She-Fa Chen; Safiyanu Muhammad Elatikpo (Mineralium Deposita, 2023)

Vegetation clumping modulates global photosynthesis through adjusting canopy light environment - Fa Li; Dalei Hao; Qing Zhu; Kunxiaojia Yuan; Renato K. Braghiere; Liming He; Xiangzhong Luo; Shanshan Wei; William J. Riley; Yelu Zeng; Min Chen (Global Change Biology, 2023)
The spatial dispersion of photoelements within a vegetation canopy, quantified by the clumping index (CI), directly regulates the within‐canopy light environment and photosynthesis rate, but is not commonly implemented in terrestrial biosphere models to estimate the ecosystem carbon cycle. A few global CI products have been developed recently with remote sensing measurements, making it possible to examine the global impacts of CI. This study deployed CI in the radiative transfer scheme of the Community Land Model version 5 (CLM5) and used the revised CLM5 to quantitatively evaluate the extent to which CI can affect canopy absorbed radiation and gross primary production (GPP), and for the first time, considering the uncertainty and seasonal variation of CI with multiple remote sensing products. Compared to the results without considering the CI impact, the revised CLM5 estimated that sunlit canopy absorbed up to 9%–15% and 23%–34% less direct and diffuse radiation, respectively, while shaded canopy absorbed 3%–18% more diffuse radiation across different biome types. The CI impacts on canopy light conditions included changes in canopy light absorption, and sunlit–shaded leaf area fraction related to nitrogen distribution and thus the maximum rate of Rubisco carboxylase activity ( V cmax ), which together decreased photosynthesis in sunlit canopy by 5.9–7.2 PgC year −1 while enhanced photosynthesis by 6.9–8.2 PgC year −1 in shaded canopy. With higher light use efficiency of shaded leaves, shaded canopy increased photosynthesis compensated and exceeded the lost photosynthesis in sunlit canopy, resulting in 1.0 ± 0.12 PgC year −1 net increase in GPP. The uncertainty of GPP due to the different input CI datasets was much larger than that caused by CI seasonal variations, and was up to 50% of the magnitude of GPP interannual variations in the tropical regions. This study highlights the necessity of considering the impacts of CI and its uncertainty in terrestrial biosphere models.

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Phylogeny, character evolution, and biogeography of the fern genus Bolbitis (Dryopteridaceae) - Li-Yun Nie; Liang Zhang; Zhen-Long Liang; Rossarin Pollawatn; Yue-Hong Yan; Ngan Thi Lu; Ralf Knapp; Xia Wan; Daniele Cicuzza; Xin-Xin Cheng; Hong-Feng Chen; Ai-Hua Wang; et al. (Molecular Phylogenetics and Evolution, 2023)

Aromatic ketone-based melamine-knitted polymers for CO2 capture and Hg2+ removal - Du Zhang; Jiajia Wang; You Wang; Yiwen Cao; Jiawei Li; Fa Zhou; Jianhan Huang; You-Nian Liu (Chemical Engineering Journal, 2023)

Isolation and Analysis of Reverse Transcriptase of Ty1-copia-Like Retrotransposons in Sugarcane - Jun-Xian Liu; Jing Liu; Tai-Yi Yang; Li-Min Liu; Li-Hang Qiu; Yi-Jing Gao; Wei-Xing Duan; Jing-Chao Lei; Hong-Jian Liu; Rong-Hua Zhang; Wei-Zhong He; Song Li; et al. (Sugar Tech, 2022)

Stochastic analysis of the variability of groundwater flow fields in heterogeneous confined aquifers of variable thickness - Ching-Min Chang; Chuen-Fa Ni; We-Ci Li; Chi-Ping Lin; I-Hsian Lee (Stochastic Environmental Research and Risk Assessment, 2022)

The brassinosteroid biosynthesis gene TaD11-2A controls grain size and its elite haplotype improves wheat grain yields - Huiyuan Xu; Han Sun; Jiajin Dong; Chengxue Ma; Jingxue Li; Zhuochun Li; Yihuan Wang; Junqi Ji; Xinrong Hu; Meihui Wu; Chunhua Zhao; Ran Qin; et al. (Theoretical and Applied Genetics, 2022)

Identification of a major stable QTL for spikelet number in wheat (Triticum aestivum L.) and its genetic effects analysis on yield-related traits - Mingsu Cao; Jizi Dong; Hao Wang; Yibiao Cai; Tianhang Ma; Xiaohan Zhou; Jingguo Xiao; Shihui Li; Linqu Chen; Huiyuan Xu; Chunhua Zhao; Yongzhen Wu; et al. (Euphytica, 2022)

Alternate freezing and thawing enhanced the sediment and nutrient runoff loss in the restored soil of the alpine mining area - Fa-Yong Li; Ren-jie Luo; Yong-jun You; Xue-fei Hu; Xiao-yan Qian; Peng-yan Zhang; Shan Wang; Guo-yu Li; Mohamed Eltohamy Kamel (Journal of Mountain Science, 2022)

Natural component plumbagin as a potential antibacterial agent against Streptococcus agalactiae infection - Ai‐Guo Huang; Lin‐Jun Su; Wei‐Hao He; Fa‐Li Zhang; Chao‐Shuai Wei; Ying‐Hui Wang (Journal of Fish Diseases, 2022)
Streptococcus agalactiae , also known as Group B Streptococcus (GBS), can infect humans, terrestrial animals and fish. The emergence of bacterial resistance of S. agalactiae to antibiotics leads to an urgent need of exploration of new antimicrobial agents. In the study, the antibacterial activity of natural component plumbagin (PLB) against S. agalactiae was investigated in vitro and in vivo. The results showed that the minimal inhibitory concentration (MIC) of PLB against S. agalactiae was 8 mg/L. The growth curve assay revealed that PLB could inhibit the growth of S. agalactiae . In addition, the time‐killing curve showed that S. agalactiae was killed almost completely by 2‐fold MIC of PLB within 12 h. Transmission electron microscopy results showed obvious severe morphological destruction and abnormal cells of S. agalactiae after treated with PLB. The pathogenicity of S. agalactiae to zebrafish was significantly decreased after preincubation with PLB for 2 h in vitro, further indicating the bactericidal activity of PLB. Interestingly, PLB could kill S. agalactiae without inducing resistance development. Furthermore, pretreatment and post‐treatment assays suggested that PLB also exhibited the antibacterial activity against S. agalactiae infection in vivo by effectively reducing the bacterial load and improving the survival rate of S. agalactiae ‐infected zebrafish. In summary, PLB had potent antibacterial activity against S. agalactiae in vitro and in vivo, and it could be an excellent antimicrobial candidate to prevent and control S. agalactiae infection.

Anterior Cingulate Cortex Mediates Hyperalgesia and Anxiety Induced by Chronic Pancreatitis in Rats - Dan Ren; Jia-Ni Li; Xin-Tong Qiu; Fa-Ping Wan; Zhen-Yu Wu; Bo-Yuan Fan; Ming-Ming Zhang; Tao Chen; Hui Li; Yang Bai; Yun-Qing Li (Neuroscience Bulletin, 2022)
Central sensitization is essential in maintaining chronic pain induced by chronic pancreatitis (CP), but cortical modulation of painful CP remains elusive. Here, we examined the role of the anterior cingulate cortex (ACC) in the pathogenesis of abdominal hyperalgesia in a rat model of CP induced by intraductal administration of trinitrobenzene sulfonic acid (TNBS). TNBS treatment resulted in long-term abdominal hyperalgesia and anxiety in rats. Morphological data indicated that painful CP induced a significant increase in FOS-expressing neurons in the nucleus tractus solitarii (NTS) and ACC, and some FOS-expressing neurons in the NTS projected to the ACC. In addition, a larger portion of ascending fibers from the NTS innervated pyramidal neurons, the neural subpopulation primarily expressing FOS under the condition of painful CP, rather than GABAergic neurons within the ACC. CP rats showed increased expression of vesicular glutamate transporter 1, and increased membrane trafficking and phosphorylation of the N -methyl-D-aspartate receptor (NMDAR) subunit NR2B and the α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid receptor (AMPAR) subunit GluR1 within the ACC. Microinjection of NMDAR and AMPAR antagonists into the ACC to block excitatory synaptic transmission significantly attenuated abdominal hyperalgesia in CP rats, which was similar to the analgesic effect of endomorphins injected into the ACC. Specifically inhibiting the excitability of ACC pyramidal cells via chemogenetics reduced both hyperalgesia and comorbid anxiety, whereas activating these neurons via optogenetics failed to aggravate hyperalgesia and anxiety in CP rats. Taken together, these findings provide neurocircuit, biochemical, and behavioral evidence for involvement of the ACC in hyperalgesia and anxiety in CP rats, as well as novel insights into the cortical modulation of painful CP, and highlights the ACC as a potential target for neuromodulatory interventions in the treatment of painful CP.

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Occurrence, source apportionment, and carcinogenic risk assessment of polycyclic aromatic hydrocarbons in urban road dusts in Shanghai - Xue-Tong Wang; Rui Fu; Ying Zhou; Cheng-Lin Wang; Guo-Fa Ren; Xiao-Li Wang; Hui Li (Environmental Science and Pollution Research, 2021)

Nitrogen contaminants damage on intestinal epithelial tight junctions: a review - Guo-ping Zhao; Jin-wang Li; Fang-wei Yang; Xiao-yu Wang; Fa-zheng Ren; Guo-fang Pang; Yi-xuan Li (Environmental Chemistry Letters, 2021)

Genome editing of Corynebacterium glutamicum mediated with Cpf1 plus Ku/LigD - Fa-Yu Yang; Nan Wei; Zhi-Hao Zhang; Mi Wang; Ying-Chun Liu; Li-Fang Zhang; Feng Gu (Biotechnology Letters, 2021)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Alkaloids with acetylcholinesterase inhibitory activity from Corydalis racemosa (Thunb.) Pers - Hui-Na Yao; Zhi-Tian Peng; Yun-Feng Zhang; Di-Fa Liu; Bing-Feng Huang; Peng-Fei Tu; Yun-Fang Zhao; Hui-Xia Huo; Jun Li (Natural Product Research, 2021)

Comparison of the Bulk and Rhizosphere Soil Prokaryotic Communities Between Wild and Reintroduced Manglietiastrum sinicum Plants, a Threatened Species with Extremely Small Populations - Dai-Fa Su; Qing-Qing Shen; Jun-Yu Yang; Zhi-Ying Li; Wei Xiao; Yong-Xia Wang; Zhang-Gui Ding; Xiao-Long Cui (Current Microbiology, 2021)

Relationship between crustal magnetic anomalies and strong earthquake activity in the south segment of the China North-South Seismic Belt - Li-Min Wen; Guo-Fa Kang; Chun-Hua Bai; Guo-Ming Gao (Applied Geophysics, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Seasonal variation of nitrogen biogeochemical processes constrained by nitrate dual isotopes in cascade reservoirs, Southwestern China - Sai-Nan Chen; Fu-Jun Yue; Xiao-Long Liu; Jun Zhong; Yuan-Bi Yi; Wan-Fa Wang; Yulin Qi; Hua-Yun Xiao; Si-Liang Li (Environmental Science and Pollution Research, 2021)

Insights on the Working Principles of Secondary Electrospray Ionization High-Resolution Mass Spectrometry for Quantitative Analysis of Aerosol Chemical Composition - Xin Xu; Jia Fa Zeng; Dan Dan Jin; Zheng Xu Huang; Lei Li; Anthony S. Wexler; Man Nin Chan; Zhen Zhou; Yong Jie Li; Xue Li (Aerosol Science and Engineering, 2021)
Real-time mass spectrometry (MS) has attracted increasing interest in environmental analysis due to its advantages in high time resolution, minimization of sampling artifact, and avoidance of time-consuming sample pretreatment. Among real-time MS methods, secondary electrospray ionization MS (SESI-MS) is showing great promise for the detection of organic compounds in atmospheric particulate matter. In this study, we demonstrated the working principles of secondary nanoelectrospray ionization (Sec-nESI) for real-time measurement of laboratory-generated organic aerosols using l -tartaric acid (TA) as a model compound. Factors affecting the detection of TA particles using a homemade Sec-nESI source coupled with a high-resolution mass spectrometer are systematically investigated. Temperature of ion transport capillary (ITC) was found to be the key factor in determining the ion signal intensity, which shows an increase of intensity by a factor of 100 from ITC temperature of 100–300 °C and could be attributed to more efficient desolvation and ionization. The characteristic fragment ion at m / z 72.99 was selected for quantitative analysis of TA at normalized collision energy of 50%, the optimal value applied during MS/MS analysis. Detection limit of 0.14 µg/m 3 and a linear range of 0.2–2.97 µg/m 3 are achieved. Satisfactory correlations between ion signal intensity and particle surface area ( R 2 = 0.969) and mass concentration ( R 2 = 0.967) were obtained. Although an equally good correlation was observed between signal intensity and particle surface area, the good correlation between signal intensity and particle mass concentration indicates that high solubility of TA ensures efficient dissolution of TA in the primary ESI droplets for further ionization.

Effect of fermentation bed on bacterial growth in the fermentation mattress material and cecum of ducks - Jian- mei Wang; Xin- meng Gan; Fa-jun Pu; Wan- xia Wang; Min Ma; Ling-li Sun; Ji-wei Hu; Bo Hu; Rong-ping Zhang; Li-li Bai; Liang Li; He-he Liu (Archives of Microbiology, 2021)

Crenobacter intestini sp. nov., Isolated from the Intestinal Tract of Konosirus punctatus - Song-Biao Shi; Jia-Fa Wu; Li-Fang Yang; Ming-Guo Jiang; Cai-Mi Gao; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Rare taxa maintain the stability of crop mycobiomes and ecosystem functions - Chao Xiong; Ji‐Zheng He; Brajesh K. Singh; Yong‐Guan Zhu; Jun‐Tao Wang; Pei‐Pei Li; Qin‐Bing Zhang; Li‐Li Han; Ju‐Pei Shen; An‐Hui Ge; Chuan‐Fa Wu; Li‐Mei Zhang (Environmental Microbiology, 2021)
Summary Plants harbour highly diverse mycobiomes which sustain essential functions for host health and productivity. However, ecological processes that govern the plant–mycobiome assembly, interactions and their impact on ecosystem functions remain poorly known. Here we characterized the ecological role and community assembly of both abundant and rare fungal taxa along the soil–plant continuums (rhizosphere, phyllosphere and endosphere) in the maize–wheat/barley rotation system under different fertilization practices at two contrasting sites. Our results indicate that mycobiome assembly is shaped predominantly by compartment niche and host species rather than by environmental factors. Moreover, crop‐associated fungal communities are dominated by few abundant taxa mainly belonging to Sordariomycetes and Dothideomycetes, while the majority of diversity within mycobiomes are represented by rare taxa. For plant compartments, the abundant sub‐community is mainly determined by stochastic processes. In contrast, the rare sub‐community is more sensitive to host selection and mainly governed by deterministic processes. Furthermore, our results demonstrate that rare taxa play an important role in fungal co‐occurrence network and ecosystem functioning like crop yield and soil enzyme activities. These results significantly advance our understanding of crop mycobiome assembly and highlight the key role of rare taxa in sustaining the stability of crop mycobiomes and ecosystem functions.

Sesquiterpenoids from the roots and rhizomes of Valeriana amurensis and their effects on NGF-induced neurite outgrowth in PC12 cells - Fa-Wu Dong; Fang Li; Jia-Jia Ren; Cheng-Mei Zhao; Hong-Li Diao; Bao-Jing Li; Yan-Ping Li; Jiang-Miao Hu; Hong-Ping He (Natural Product Research, 2021)

Delayed association of acute particulate matter 2.5 air pollution exposure with loss of complexity in cardiac rhythm dynamics: insight from detrended fluctuation analysis - Tsung-Ying Tsai; Li-Wei Lo; Shin-Huei Liu; Wen-Han Cheng; Yu-Hui Chou; Wei-Lun Lin; Yenn-Jiang Lin; Shih-Lin Chang; Yu-Feng Hu; Fa-Po Chung; Jo-Nan Liao; Tze-Fan Chao; et al. (Environmental Science and Pollution Research, 2021)

Recycling of subducted Indian continental crust and its significance on post-collisional ultrapotassic magmatism in southwestern Tibet - Izhar Sadiq; Fa-Bin Pan; Hong-Fei Zhang; Chun-Feng Li; Biji Luo; Mohammad Arif (Contributions to Mineralogy and Petrology, 2021)

Multichannel deconvolution with spatial reflection regularization - Li Hao; Li Guo-Fa; Ma Xiong; Zhang Jia-Liang; Meng Qing-Long; Zhang Zhu-Xin (Applied Geophysics, 2021)

Preliminary report on the improved resistance towards Pseudomonas syringae pv. actinidiae of cultivated kiwifruit (Actinidia chinensis) when grafted onto wild Actinidia guilinensis rootstock in vitro - Fa-ming Wang; Jie-wei Li; Kai-yu Ye; Hong-juan Gong; Ping-ping Liu; Qiao-sheng Jiang; Bei-bei Qi; Quan-hui Mo (Journal of Plant Pathology, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Diversity and potential biogeochemical impacts of viruses in bulk and rhizosphere soils - Li Bi; Dan‐Ting Yu; Shuai Du; Li‐Mei Zhang; Li‐Yu Zhang; Chuan‐Fa Wu; Chao Xiong; Li‐Li Han; Ji‐Zheng He (Environmental Microbiology, 2021)
Summary Viruses can affect microbial dynamics, metabolism and biogeochemical cycles in aquatic ecosystems. However, viral diversity and functions in agricultural soils are poorly known, especially in the rhizosphere. We used virome analysis of eight rhizosphere and bulk soils to study viral diversity and potential biogeochemical impacts in an agro‐ecosystem. The order Caudovirales was the predominant viral type in agricultural soils, with Siphoviridae being the most abundant family. Phylogenetic analysis of the terminase large subunit of Caudovirales identified high viral diversity and three novel groups. Viral community composition differed significantly between bulk and rhizosphere soils. Soil pH was the main environmental driver of the viral community structure. Remarkably, abundant auxiliary carbohydrate‐active enzyme (CAZyme) genes were detected in viromes, including glycoside hydrolases, carbohydrate esterases and carbohydrate‐binding modules. These results demonstrate that virus‐encoded putative auxiliary metabolic genes or metabolic genes that may change bacterial metabolism and indirectly contribute to biogeochemical cycling, especially carbon cycling, in agricultural soil.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Development and application of iterative facies-constrained seismic inversion - Huang Xu-Ri; Li Li; Li Fa-Lv; Li Xi-Sheng; Chen Qi; Dai Yue (Applied Geophysics, 2020)

Nonstationary signal inversion based on shaping regularization for random noise attenuation - Wu-Yang Yang; Wei Wang; Guo-Fa Li; Xin-Jian Wei; Wan-Li Wang; De-wu Chen (Applied Geophysics, 2020)

Comparative analysis and natural evolution of squalene epoxidase in three Fritillaria species - Xu Lu; Lin-Ning Zhang; Jin-Fa Du; Xiao-Yan Zheng; Hui-Jun Li; Ping Li; Gui-Zhong Xin; Yan Jiang (Plant Molecular Biology, 2020)

Roles of sulfur compounds in growth and alkaline phosphatase activities of Microcystis aeruginosa under phosphorus deficiency stress - En Xie; Fangfang Li; Chaozi Wang; Wei Shi; Chen Huang; Keyu Fa; Xiao Zhao; Dayi Zhang (Environmental Science and Pollution Research, 2020)

Method for obtaining high-resolution velocity spectrum based on weighted similarity - Xing-Rong Xu; Qin Su; Jun-Fa Xie; Jing Wang; Long-Jiang Kou; Meng-Li Liu (Applied Geophysics, 2020)

Evaluating the effects of transgenic Bt rice cultivation on soil stability - Ying-ying Song; Jia-wen Liu; Li-kun Li; Man-qiang Liu; Xiao-yun Chen; Fa-jun Chen (Environmental Science and Pollution Research, 2020)

Tenuazonic acid-induced change in volatile emission from rose plants and its chemometrical analysis - Fa-zhong Yang; Yun-xian Li; Min Tang; Guo-lei Zhu; Shi-ping Zhou; Bin Yang (Journal of Plant Diseases and Protection, 2020)

Bioavailable phosphorus distribution in alpine meadow soil is affected by topography in the Tian Shan Mountains - Fa-Yong Li; Cheng-yu Yuan; Zi-Qiang Yuan; Yong-jun You; Xue-fei Hu; Shan Wang; Guo-yu Li (Journal of Mountain Science, 2020)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

Toxicity, residue, degradation and detection methods of the insecticide triazophos - Fang-Wei Yang; Yi-Xuan Li; Fa-Zheng Ren; Ran Wang; Guo-Fang Pang (Environmental Chemistry Letters, 2019)

Association of the Polygenic Risk Score with the Incidence Risk of Parkinson’s Disease and Cerebrospinal Fluid α-Synuclein in a Chinese Cohort - Wei-Wei Li; Dong-Yu Fan; Ying-Ying Shen; Fa-Ying Zhou; Yang Chen; Ye-Ran Wang; Heng Yang; Jing Mei; Ling Li; Zhi-Qiang Xu; Yan-Jiang Wang (Neurotoxicity Research, 2019)

Genetic Association Between NGFR, ADAM17 Gene Polymorphism, and Parkinson’s Disease in the Chinese Han Population - Wei-Wei Li; Ying-Ying Shen; Dong-Wan Chen; Hui-Yun Li; Qian-Qian Shi; Jing Mei; Heng Yang; Fa-Ying Zhou; An-Yu Shi; Tao Zhang; Xiu-Qing Yao; Zhi-Qiang Xu; et al. (Neurotoxicity Research, 2019)

Assessing the influence of the minimum measured diameter on forest spatial patterns and nearest neighborhood relationships - Yuan-fa Li; Hai-peng Yang; Hong-xiang Wang; Shao-ming Ye; Wen-zhen Liu (Journal of Mountain Science, 2019)

Ottowia flava sp. nov., isolated from fish intestines - Song-Biao Shi; Gui-Ding Li; Li-Fang Yang; Cong Liu; Ming-Guo Jiang; Qin-Yuan Li; Jia-Fa Wu; Kun Zhang; Long-Qian Jiang; Nai-Kun Shen; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Displacement characteristics and prediction of Baishuihe landslide in the Three Gorges Reservoir - De-ying Li; Yi-qing Sun; Kun-long Yin; Fa-sheng Miao; Thomas Glade; Chin Leo (Journal of Mountain Science, 2019)

Three-dimensional identification of hydrological drought and multivariate drought risk probability assessment in the Luanhe River basin, China - Xu Chen; Fa-wen Li; Jian-zhu Li; Ping Feng (Theoretical and Applied Climatology, 2019)

Modeling Alzheimer’s Disease by Induced Pluripotent Stem Cells Carrying APP D678H Mutation - Kuo-Hsuan Chang; Guey-Jen Lee-Chen; Ching-Chang Huang; Jia-Li Lin; Yi-Jing Chen; Pei-Chi Wei; Yen-Shi Lo; Chin-Fa Yao; Ming-Wei Kuo; Chiung-Mei Chen (Molecular Neurobiology, 2019)

Reference evapotranspiration concentration and its relationship with precipitation concentration at southern and northern slopes of Tianshan Mountains, China - Fa-rong Huang; Tao Yang; Qian Li; Si-si Li; Lan-hai Li; Suwannee Adsavakulchai (Journal of Mountain Science, 2019)

Influence of permeation effect on the microfabric of the slip zone soils: A case study from the Huangtupo landslide - Fa-sheng Miao; Yi-ping Wu; Yuan-hua Xie; Lin-wei Li; Jie Li; Lei Huang (Journal of Mountain Science, 2019)

Portable vertical pendulum tiltmeter development and application test - Jie-ning Xia; Qiang Lin; Li-Xia Geng; Zhen Li; Song Luo; Nong-Fa Li; Jian-Feng Yu; Jun Liu (Acta Geodaetica et Geophysica, 2019)

Integration of white shrimp (Litopenaeus vannamei) and green seaweed (Ulva prolifera) in minimum-water exchange aquaculture system - Hong-xing Ge; Qian Ni; Jian Li; Ji-tao Li; Zhao Chen; Fa-zhen Zhao (Journal of Applied Phycology, 2019)

Nonstationary inversion-based directional deconvolution of airgun array signature - Hao Li; Guo-Fa Li; Xiang-Hui Guo; Xi-Ping Sun; Jian-Fu Wang (Applied Geophysics, 2019)

Numerical assessments of recharge-dominated groundwater flow and transport in the nearshore reclamation area in western Taiwan - Chuen-Fa Ni; Wei-Ci Li; Shaohua Marko Hsu; I-Hsien Lee; Chi-Ping Lin (Environmental Monitoring and Assessment, 2019)

The Role of miR-150 in Stress-Induced Anxiety-Like Behavior in Mice - Wen-Juan Zhang; Wen-Yu Cao; Yan-Qing Huang; Yan-Hui Cui; Bo-Xuan Tu; Lai-Fa Wang; Guang-Jing Zou; Yu Liu; Zhao-Lan Hu; Rong Hu; Chang-Qi Li; Xiao-Wei Xing; et al. (Neurotoxicity Research, 2019)

Identification of QTL regions for seedling root traits and their effect on nitrogen use efficiency in wheat (Triticum aestivum L.) - Xiaoli Fan; Wei Zhang; Na Zhang; Mei Chen; Shusong Zheng; Chunhua Zhao; Jie Han; Jiajia Liu; Xilan Zhang; Liqiang Song; Jun Ji; Xigang Liu; et al. (Theoretical and Applied Genetics, 2018)

QTL for flag leaf size and their influence on yield-related traits in wheat - Chunhua Zhao; Yinguang Bao; Xiuqin Wang; Haitao Yu; Anming Ding; Chunhui Guan; Junpeng Cui; Yongzhen Wu; Han Sun; Xingfeng Li; Dongfeng Zhai; Linzhi Li; et al. (Euphytica, 2018)

Associations of HSP90AA2 gene polymorphisms with disease susceptibility, glucocorticoids efficacy and health-related quality of life in Chinese systemic lupus erythematosus patients - Man Zhang; Su-Su Li; Qiao-Mei Xie; Jian-Hua Xu; Xiu-Xiu Sun; Fa-Ming Pan; Sheng-Qian Xu; Sheng-Xiu Liu; Jin-Hui Tao; Shuang Liu; Jing Cai; Pei-Ling Chen; et al. (Genes & Genomics, 2018)

Pre-Injection of Small Interfering RNA (siRNA) Promotes c-Jun Gene Silencing and Decreases the Survival Rate of Axotomy-Injured Spinal Motoneurons in Adult Mice - Ying-qin Li; Fa-huan Song; Ke Zhong; Guang-yin Yu; Prince Last Mudenda Zilundu; Ying-ying Zhou; Rao Fu; Ying Tang; Ze-min Ling; Xiaoying Xu; Li-hua Zhou (Journal of Molecular Neuroscience, 2018)

Avalanche activity and characteristics of its triggering factors in the western Tianshan Mountains, China - Jian-sheng Hao; Fa-rong Huang; Yang Liu; Chukwudi Amanambu Amobichukwu; Lan-hai Li (Journal of Mountain Science, 2018)

Fast local wavenumber (FLW) method for the inversion of magnetic source parameters - Guo-Qing Ma; Yan-Bo Ming; Jiang-Tao Han; Li-Li Li; Qing-Fa Meng (Applied Geophysics, 2018)

The effects of rainfall regimes and terracing on runoff and erosion in the Three Gorges area, China - Qin-xue Xu; Pan Wu; Jun-feng Dai; Tian-wei Wang; Zhao-xia Li; Chong-fa Cai; Zhi-hua Shi (Environmental Science and Pollution Research, 2018)

Spatiotemporal variation of hydrological drought based on the Optimal Standardized Streamflow Index in Luanhe River basin, China - Xu Chen; Fa-wen Li; Ping Feng (Natural Hazards, 2018)

Cytotoxicity in vitro, cellular uptake, localization and apoptotic mechanism studies induced by ruthenium(II) complex - Jincan Chen; Yao Zhang; Guodong Li; Fa Peng; Xinming Jie; Ji She; Guangzhi Dongye; Zhilin Zou; Shiwen Rong; Lanmei Chen (JBIC Journal of Biological Inorganic Chemistry, 2018)

Significant genetic association of a functional TFPI variant with circulating fibrinogen levels and coronary artery disease - Duraid Hamid Naji; Chengcheng Tan; Fabin Han; Yuanyuan Zhao; Junhan Wang; Dan Wang; Jingjing Fa; Sisi Li; Shanshan Chen; Qiuyun Chen; Chengqi Xu; Qing K. Wang (Molecular Genetics and Genomics, 2018)

Effect of dietary phospholipid levels on growth, lipid metabolism, and antioxidative status of juvenile hybrid snakehead (Channa argus×Channa maculata) - Shi-Mei Lin; Fa-Jian Li; Bundit Yuangsoi; Sompong Doolgindachbaporn (Fish Physiology and Biochemistry, 2018)

Inversion-based data-driven time-space domain random noise attenuation method - Yu-Min Zhao; Guo-Fa Li; Wei Wang; Zhen-Xiao Zhou; Bo-Wen Tang; Wen-Bo Zhang (Applied Geophysics, 2017)

Near-source noise suppression of AMT by compressive sensing and mathematical morphology filtering - Guang Li; Xiao Xiao; Jing-Tian Tang; Jin Li; Hui-Jie Zhu; Cong Zhou; Fa-Bao Yan (Applied Geophysics, 2017)

Comprehensive risk assessment and source identification of selected heavy metals (Cu, Cd, Pb, Zn, Hg, As) in tidal saltmarsh sediments of Shuangtai Estuary, China - Chang-Fa Liu; Bing Li; Yi-Ting Wang; Yuan Liu; Heng-Jiang Cai; Hai-Feng Wei; Jia-Wen Wu; Jin Li (Environmental Monitoring and Assessment, 2017)

A potent indolylquinoline alleviates growth of human lung cancer cell tumorspheres - Yu-Ling Ni; Chang-Hung Hsieh; Seung-Hun Kim; Jing-Ping Wang; Chun-Li Su; Ching-Fa Yao; Kang Fang (Apoptosis, 2017)

Erratum to: Prostaglandin actions in established insect cell lines - Yao-Fa Li; Hongwei Zhang; Joseph A. Ringbauer; Cynthia L. Goodman; Tamra Reall Lincoln; Kaile Zhou; David Stanley (In Vitro Cellular & Developmental Biology - Animal, 2017)

Taxonomy of the order Mononegavirales: update 2017 - Gaya K. Amarasinghe; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Martin Beer; Nicolás Bejerman; Kim R. Blasdell; Alisa Bochnowski; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; Kartik Chandran; et al. (Archives of Virology, 2017)

Characterization of the temporal and spatial expression of wheat (Triticum aestivum L.) plant height at the QTL level and their influence on yield-related traits - Na Zhang; Xiaoli Fan; Fa Cui; Chunhua Zhao; Wei Zhang; Xueqiang Zhao; Lijuan Yang; Ruiqing Pan; Mei Chen; Jie Han; Jun Ji; Dongcheng Liu; et al. (Theoretical and Applied Genetics, 2017)

Prostaglandin actions in established insect cell lines - Yao-Fa Li; Hongwei Zhang; Joseph A. Ringbauer; Cynthia L. Goodman; Tamra Reall Lincoln; Kaile Zhou; David Stanley (In Vitro Cellular & Developmental Biology - Animal, 2017)

Cell lines derived from the squash bug, Anasa tristis (Coreidae: Hemiptera) - Cynthia L. Goodman; Joseph A. Ringbauer; Yao-Fa Li; Tamra Reall Lincoln; David Stanley (In Vitro Cellular & Developmental Biology - Animal, 2017)

A Novel Wheat Nicotianamine Synthase Gene, TaNAS-D, Confers High Salt Tolerance in Transgenic Arabidopsis - Jie Han; Wei Zhang; Lijing Sun; Qiannan Su; Zijing Li; Xiaoli Fan; Na Zhang; Ruiqing Pan; Fa Cui; Jun Ji; Hui Li; Junming Li (Plant Molecular Biology Reporter, 2017)

Associations Between Hepatic Functions and Plasma Amyloid-Beta Levels—Implications for the Capacity of Liver in Peripheral Amyloid-Beta Clearance - Ye-Ran Wang; Qing-Hua Wang; Tao Zhang; Yu-Hui Liu; Xiu-Qing Yao; Fan Zeng; Jing Li; Fa-Yin Zhou; Lin Wang; Jia-Chuan Yan; Hua-Dong Zhou; Yan-Jiang Wang (Molecular Neurobiology, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

GPR30 Activation Contributes to the Puerarin-Mediated Neuroprotection in MPP+-Induced SH-SY5Y Cell Death - Yue-Fa Cheng; Guoqi Zhu; Qing-Wen Wu; Yue-Sheng Xie; Yan Jiang; Lan Guo; Ya-Li Guan; Ying-Shuo Liu; Jun Zhang (Journal of Molecular Neuroscience, 2017)

Attraction of Coffee Bean Weevil, Araecerus fasciculatus, to Volatiles from the Industrial Yeast Kluyveromyces lactis - Shuai Yang; Xiang-Dong Mei; Xiao-Fang Zhang; Yao-Fa Li; Dongmei She; Tao Zhang; Jun Ning (Journal of Chemical Ecology, 2017)

Tenuigenin promotes the osteogenic differentiation of bone mesenchymal stem cells in vitro and in vivo - Hua-ji Jiang; Xing-gui Tian; Shou-bin Huang; Guo-rong Chen; Min-jun Huang; Yu-hui Chen; Bin Yan; Sheng-fa Li; Jia-jun Tang; Hui-yu Zhao; Liang Wang; Zhong-min Zhang (Cell and Tissue Research, 2017)

Transcriptome analysis of Dlm mutants reveals the potential formation mechanism of lesion mimic in wheat - Lei Li; Xuan Shi; Fei Zheng; Di Wu; Ai-Ai Li; Fa-Yu Sun; Chang-Cheng Li; Jin-Cai Wu; Tao Li (European Journal of Plant Pathology, 2016)

Parallel viewshed analysis on a PC cluster system using triple-based irregular partition scheme - Xiao-Dong Song; Guo-An Tang; Xue-Jun Liu; Wan-Feng Dou; Fa-Yuan Li (Earth Science Informatics, 2016)

Alterations to biological soil crusts with alpine meadow retrogressive succession affect seeds germination of three plant species - Yi-kang Li; Jing-zheng Ouyang; Li Lin; Xing-liang Xu; Fa-wei Zhang; Yan-gong Du; Shu-li Liu; Guang-min Cao; Fa Han (Journal of Mountain Science, 2016)

Distribution of soil carbon in different grassland types of the Qinghai-Tibetan Plateau - Shu-li Liu; Yan-gong Du; Fa-wei Zhang; Li Lin; Yi-kang Li; Xiao-wei Guo; Qian Li; Guang-min Cao (Journal of Mountain Science, 2016)

Dietary lipid concentrations influence growth, liver oxidative stress, and serum metabolites of juvenile hybrid snakehead (Channa argus × Channa maculata) - Peng-Fei Zhao; Fa-Jian Li; Xiao-Ru Chen; Yong-Jun Chen; Shi-Mei Lin; Lu Zhang; Yun Li (Aquaculture International, 2016)

Taxonomy of the order Mononegavirales: update 2016 - Claudio L. Afonso; Gaya K. Amarasinghe; Krisztián Bányai; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Nicolás Bejerman; Kim R. Blasdell; François-Xavier Briand; Thomas Briese; Alexander Bukreyev; Charles H. Calisher; et al. (Archives of Virology, 2016)

A new cytotoxic biflavonoid from the rhizome of Wikstroemia indica - Meng Shao; Xiao-Jun Huang; Jun-Shan Liu; Wei-Li Han; Hong-Bing Cai; Qing-Fa Tang; Qin Fan (Natural Product Research, 2016)

A novel process for obtaining pinosylvin using combinatorial bioengineering in Escherichia coli - Jing-long Liang; Li-qiong Guo; Jun-fang Lin; Ze-qi He; Fa-ji Cai; Jun-fei Chen (World Journal of Microbiology and Biotechnology, 2016)

Contribution of aboveground litter to soil respiration in Populus davidiana Dode plantations at different stand ages - Xin Zhao; Fa-dong Li; Wan-jun Zhang; Zhi-pin Ai (Journal of Mountain Science, 2016)

Effects of hydrogeological properties on sea-derived benzene transport in unconfined coastal aquifers - Wei-Ci Li; Chuen-Fa Ni; Chia-Hsing Tsai; Yi-Ming Wei (Environmental Monitoring and Assessment, 2016)

Autophagy Promotes Peripheral Nerve Regeneration and Motor Recovery Following Sciatic Nerve Crush Injury in Rats - Hai-cheng Huang; Li Chen; Hai-xing Zhang; Sheng-fa Li; Pei Liu; Tian-yun Zhao; Chuan-xiang Li (Journal of Molecular Neuroscience, 2016)
Autophagy maintains cellular homeostasis by stimulating the lysosomal degradation of cytoplasmic structures, including damaged organelles and dysfunctional proteins. The role of autophagy in the renewal and regeneration of injured peripheral nerves remains poorly understood. The current study investigated the role of autophagy in peripheral nerve regeneration and motor function recovery following sciatic nerve crush injury in rats by stimulating or suppressing autophagy and detecting the presence of autophagosomes and LC3-II expression by electron microscopy and Western blotting, respectively. Neurobehavioral function was tested by CatWalk gait analysis 1, 2, 3, and 6 weeks after injury, and the expression of neurofilament (NF)-200 and myelin basic protein (MBP) at the injury site was examined by immunocytochemistry. Apoptosis at the lesion site was determined by the terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Treatment of injured rats with the autophagy inducer rapamycin increased the number of autophagosomes and LC3-II expression while reducing the number of apoptotic cells at the lesion; this was associated with an upregulation of MBP and NF-200 expression and increased motor function recovery as compared to sham-operated rats and those that were subjected to crush injury but untreated. The opposite effects were observed in rats treated with the autophagy inhibitor 3-methyladenine. These data indicate that the modulation of autophagy in peripheral nerve injury could be an effective pharmacological approach to promote nerve regeneration and reestablish motor function.

QTL detection for wheat kernel size and quality and the responses of these traits to low nitrogen stress - Fa Cui; Xiaoli Fan; Mei Chen; Na Zhang; Chunhua Zhao; Wei Zhang; Jie Han; Jun Ji; Xueqiang Zhao; Lijuan Yang; Zongwu Zhao; Yiping Tong; et al. (Theoretical and Applied Genetics, 2016)

2.5D forward modeling and inversion of frequency-domain airborne electromagnetic data - Wen-Ben Li; Zhao-Fa Zeng; Jing Li; Xiong Chen; Kun Wang; Zhao Xia (Applied Geophysics, 2016)

Tomographic inversion of near-surface Q factor by combining surface and cross-hole seismic surveys - Guo-Fa Li; Hao Zheng; Wen-Liang Zhu; Ming-Chao Wang; Tong-Li Zhai (Applied Geophysics, 2016)

Geophone-seabed coupling effect and its correction - Bao-Qing Zhang; Hui Zhou; Guo-Fa Li; Jian-Qing Guo (Applied Geophysics, 2016)

Petrology and Spectroscopy Studies on Danxia Geoheritage in Southeast Sichuan Area, China: Implications for Danxia Surveying and Monitoring - Jun-Ting Qiu; Peng-Ju Li; Zhang-Fa Yu; Ping Li (Geoheritage, 2015)

Wide-angle incidence and P-wave transmission - Jun-Fa Xie; Cheng-Yu Sun; Mei-Yan Lin; Jing-Jing Li (Applied Geophysics, 2015)

Recursive impedance inversion of ground-penetrating radar data in stochastic media - Zhao-Fa Zeng; Xiong Chen; Jing Li; Ling-Na Chen; Qi Lu; Feng-Shan Liu (Applied Geophysics, 2015)

Removal efficiencies for 136 tetra- through octa-chlorinated dibenzo-p-dioxins and dibenzofuran congeners with activated carbons - Xu-Jian Zhou; Xiao-Dong Li; Ming-Jiang Ni; Ke-Fa Cen (Environmental Science and Pollution Research, 2015)

High-speed ring shear tests to study the motion and acceleration processes of the Yingong landslide - Ming-jian Hu; Hua-li Pan; Chang-qi Zhu; Fa-wu Wang (Journal of Mountain Science, 2015)

An indolylquinoline derivative promotes apoptosis in human lung cancer cells by impairing mitochondrial functions - Chun-Yen Liu; Pei-Tsen Wu; Jing-Ping Wang; Po-Wei Fan; Chang-Hung Hsieh; Chun-Li Su; Chien-Chih Chiu; Ching-Fa Yao; Kang Fang (Apoptosis, 2015)

Endoplasmic Reticulum Protein 29 Protects Axotomized Neurons from Apoptosis and Promotes Neuronal Regeneration Associated with Erk Signal - Yun-Hui Zhang; Visar Belegu; Yu Zou; Fang Wang; Bao-Jiang Qian; Ran Liu; Ping Dai; Wei Zhao; Fa-Bao Gao; Lei Wang; Li-Mei Cao; John W. McDonald; et al. (Molecular Neurobiology, 2015)

Potential dental pulp revascularization and odonto-/osteogenic capacity of a novel transplant combined with dental pulp stem cells and platelet-rich fibrin - Yong-Jin Chen; Yin-Hua Zhao; Ya-Juan Zhao; Nan-Xia Liu; Xin Lv; Qiang Li; Fa-Ming Chen; Min Zhang (Cell and Tissue Research, 2015)

Lampropedia puyangensis sp. nov., isolated from symptomatic bark of Populus × euramericana canker and emended description of Lampropedia hyalina (Ehrenberg 1832) Lee et al. 2004 - Yong Li; Tao Wang; Chun-gen Piao; Lai-fa Wang; Guo-zhong Tian; Tian-hui Zhu; Min-wei Guo (Antonie van Leeuwenhoek, 2015)

Novel calicivirus from a ferret badger (Melogale moschata) in China - Fa-Ming Miao; Yue-Hong Li; Ye Liu; Shou-Feng Zhang; Fu-Chun Miao; Jing-Hui Zhao; Rong-Liang Hu (Archives of Virology, 2015)

Characterization of mineralogy and surface zeta potential of atmospheric dust fall in northwest China - Fa-Qin Dong; Wu Chen; Qun-Wei Dai; Yue-Quan Deng; Ping He; Xiao-Chun He; Jun Tang; Li-Zhu Liu; Hua He (Mineralogy and Petrology, 2015)

Alternaria toxin-induced resistance in rose plants against rose aphid (Macrosiphum rosivorum): effect of tenuazonic acid - Fa-zhong Yang; Bin Yang; Bei-bei Li; Chun Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

Genetic polymorphisms of CYP2D6*10 and the effectiveness of combined tamoxifen citrate and testosterone undecanoate treatment in infertile men with idiopathic oligozoospermia - Kai-fa Tang; Yi-li Zhao; Shang-shu Ding; Qi-fei Wu; Xing-yang Wang; Jia-qi Shi; Fa Sun; Jun-ping Xing (Journal of Zhejiang University-SCIENCE B, 2015)

Early-life sleep deprivation persistently depresses melatonin production and bio-energetics of the pineal gland: potential implications for the development of metabolic deficiency - Li-You Chen; Cheng Tiong; Chung-Hung Tsai; Wen-Chieh Liao; Shun-Fa Yang; Su-Chung Youn; Fu-Der Mai; Hung-Ming Chang (Brain Structure and Function, 2015)

Random noise attenuation by f-x spatial projection-based complex empirical mode decomposition predictive filtering - Yan-Yan Ma; Guo-Fa Li; Yao-Jun Wang; Hui Zhou; Bao-Jiang Zhang (Applied Geophysics, 2015)

Determination of royal jelly freshness by ELISA with a highly specific anti-apalbumin 1, major royal jelly protein 1 antibody - Li-rong Shen; Yi-ran Wang; Liang Zhai; Wen-xiu Zhou; Liang-liang Tan; Mei-lu Li; Dan-dan Liu; Fa Xiao (Journal of Zhejiang University-SCIENCE B, 2015)

A novel strategy for rapid quantification of 20( S )-protopanaxatriol and 20( S )-protopanaxadiol saponins in Panax notoginseng P. ginseng and P. quinquefolium - Fa-Xiang Xu; Cen Yuan; Jian-Bo Wan; Ru Yan; Hao Hu; Shao-Ping Li; Qing-Wen Zhang (Natural Product Research, 2015)

Retrieving three-dimensional displacement fields of mining areas from a single InSAR pair - Zhi Wei Li; Ze Fa Yang; Jian Jun Zhu; Jun Hu; Yun Jia Wang; Pei Xian Li; Guo Liang Chen (Journal of Geodesy, 2015)

Paenibacillus abyssi sp. nov., isolated from an abyssal sediment sample from the Indian Ocean - Xiao-Fang Huang; Fa-Zuo Wang; Wei Zhang; Jie Li; Juan Ling; Jian Yang; Jun-De Dong; Xin-Peng Tian (Antonie van Leeuwenhoek, 2014)

Testing hypotheses of mitochondrial gene‐tree paraphyly: unravelling mitochondrial capture of the Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) by the Taiwan Scimitar Babbler ( P omatorhinus musicus ) - Feng Dong; Fa‐Sheng Zou; Fu‐Min Lei; Wei Liang; Shou‐Hsien Li; Xiao‐Jun Yang (Molecular Ecology, 2014)
Species‐level paraphyly inferred from mitochondrial gene trees is a prevalent phenomenon in taxonomy and systematics, but there are several potential causes that are not easily explained by currently used methods. This study aimed to test the underlying causes behind the observed paraphyly of Streak‐breasted Scimitar Babbler ( P omatorhinus ruficollis ) via statistical analyses of four mitochondrial (mt DNA ) and nine nuclear (nu DNA ) genes. Mitochondrial gene trees show paraphyly of P . ruficollis with respect to the Taiwan Scimitar Babbler ( P omatorhinus musicus ), but nuclear genealogies support a sister‐group relationship. Predictive coalescent simulations imply several hypothetical explanations, the most likely being mitochondrial capture of P . ruficollis by P . musicus for the observed cyto‐nuclear incongruence. Further approximate Bayesian computation suggests a unidirectional introgression model with substantial level of gene flow from P . ruficollis to P . musicus during their initial divergence during the Late Pleistocene. This specific observation frames several potential causes for incongruent outcomes of mitochondrial and nuclear introgression in general, and on the whole, our results underscore the strength of multiple independent loci for species delimitation and importance of testing hypotheses that explain disparate causes of mitochondrial gene‐tree paraphyly.

A down-regulated epi-allele of the genomes uncoupled 4 gene generates a xantha marker trait in rice - Rui-Qing Li; Jian-Zhong Huang; Hai-Jun Zhao; Hao-Wei Fu; You-Fa Li; Guo-Zhen Liu; Qing-Yao Shu (Theoretical and Applied Genetics, 2014)

Snake model for the extraction of loess shoulder-line from DEMs - Shi-jiang Yan; Guo’an Tang; Fa-yuan Li; Lei Zhang (Journal of Mountain Science, 2014)

Cerebral hemodynamic characteristics of acute mountain sickness upon acute high-altitude exposure at 3,700 m in young Chinese men - Shi-Zhu Bian; Jun Jin; Qian-Ning Li; Jun Qin; Ji-Hang Zhang; Shi-Yong Yu; Jian-Fei Chen; Cai-Fa Tang; Lan Huang (European Journal of Applied Physiology, 2014)

The expression and functional role of a FOXC1 related mRNA-lncRNA pair in oral squamous cell carcinoma - Xiang-pan Kong; Jie Yao; Wei Luo; Fu-kui Feng; Jun-tao Ma; Yi-peng Ren; De-li Wang; Rong-fa Bu (Molecular and Cellular Biochemistry, 2014)

Isolation and characterization of microsatellite loci in Euphorbia lamarckii Sweet (Euphorbiaceae) from the Canary Islands - Yan-Shu Li; Ye Sun; Fa-Guo Wang; Fu-Wu Xing (Conservation Genetics Resources, 2014)

Construction of an integrative linkage map and QTL mapping of grain yield-related traits using three related wheat RIL populations - Fa Cui; Chunhua Zhao; Anming Ding; Jun Li; Lin Wang; Xingfeng Li; Yinguang Bao; Junming Li; Honggang Wang (Theoretical and Applied Genetics, 2014)

Establishment and characterization of dairy cow growth hormone secreting anterior pituitary cell model - Jian-Fa Wang; Shou-Peng Fu; Su-Nan Li; Zhan-Qing Yang; Wen-Jing Xue; Zhi-Qiang Li; Wei Wang; Ju-Xiong Liu (In Vitro Cellular & Developmental Biology - Animal, 2014)

Identification of a novel frameshift mutation in PITX2 gene in a Chinese family with Axenfeld-Rieger syndrome - Hou-Fa Yin; Xiao-Yun Fang; Chong-Fei Jin; Jin-Fu Yin; Jin-Yu Li; Su-Juan Zhao; Qi Miao; Feng-Wei Song (Journal of Zhejiang University-SCIENCE B, 2014)

Accumulation of mercury in rice grain and cabbage grown on representative Chinese soils - Chun-fa Liu; Cheng-xian Wu; Muhammad T. Rafiq; Rukhsanda Aziz; Dan-di Hou; Zhe-li Ding; Zi-wen Lin; Lin-jun Lou; Yuan-yuan Feng; Ting-qiang Li; Xiao-e Yang (Journal of Zhejiang University-SCIENCE B, 2013)

Analysis of radial basis function interpolation approach - You-Long Zou; Fa-Long Hu; Can-Can Zhou; Chao-Liu Li; Keh-Jim Dunn (Applied Geophysics, 2013)

Molecular characterization and tissue localization of sensory neuron membrane protein from Chinese honey bee, Apis cerana cerana (Hymenoptera: Apidae) - Ying-Ying Hu; Shu-Fa Xu; Abebe Jenberie Wubie; Wei Li; Jia-Xing Huang; Zhan-Bao Guo; Ting Zhou (Applied Entomology and Zoology, 2013)

Bacillus oceani sp. nov., a new slightly halophilic bacterium, isolated from a deep sea sediment environment - Yu-Juan Liu; Li-Juan Long; Xiao-Fang Huang; Zhi-Qing You; Fa-Zuo Wang; Jie Li; Chang-Jin Kim; Xin-Peng Tian; Si Zhang (Antonie van Leeuwenhoek, 2013)

Relations between stimulation of mesolimbic dopamine and place conditioning in rats produced by cocaine or drugs that are tolerant to dopamine transporter conformational change - Gianluigi Tanda; Su Min Li; Maddalena Mereu; Alexandra M. Thomas; Aaron L. Ebbs; Lauren E. Chun; Valeria Tronci; Jennifer L. Green; Mu-Fa Zou; Theresa A. Kopajtic; Amy Hauck Newman; Jonathan L. Katz (Psychopharmacology, 2013)

Climate change trend in China, with improved accuracy - Tian-Xiang Yue; Na Zhao; R. Douglas Ramsey; Chen-Liang Wang; Ze-Meng Fan; Chuan-Fa Chen; Yi-Min Lu; Bai-Lian Li (Climatic Change, 2013)

Association of TGF-β1 +869C/T promoter polymorphism with susceptibility to autoimmune diseases: a meta-analysis - Li Zhang; Jun-wei Yan; Ying-Xin Wang; Ya-nan Wan; Jian-ping Li; Ping Liu; Bin Xu; Bing-xiang Wang; Wen-jia Peng; Fa-ming Pan; Jing Wang (Molecular Biology Reports, 2013)

Stereoselective syntheses of functionalized spirocyclopenteneoxindoles via triphenylphosphine-catalyzed [3+2] cycloaddition reactions - Qing-Fa Zhou; Xue-Ping Chu; Fei-Fei Ge; Cheng Li; Tao Lu (Molecular Diversity, 2013)

Conditional and unconditional QTL mapping of drought-tolerance-related traits of wheat seedling using two related RIL populations - HONG ZHANG; FA CUI; LIN WANG; JUN LI; ANMING DING; CHUNHUA ZHAO; YINGUANG BAO; QIUPING YANG; HONGGANG WANG (Journal of Genetics, 2013)

Iodine Excess Induces Hepatic Steatosis Through Disturbance of Thyroid Hormone Metabolism Involving Oxidative Stress in BaLB/c Mice - Yun Xia; Wei Qu; Li-Na Zhao; Hao Han; Xue-Feng Yang; Xiu-Fa Sun; Li-Ping Hao; Jian Xu (Biological Trace Element Research, 2013)

Experimental analysis and application of sparsity constrained deconvolution - Guo-Fa Li; De-Hai Qin; Geng-Xin Peng; Ying Yue; Tong-Li Zhai (Applied Geophysics, 2013)

Intergeneric hybrid between Chrysanthemum × morifolium and Artemisia japonica achieved via embryo rescue shows salt tolerance - Wen-ying Zhu; Jia-fu Jiang; Su-mei Chen; Liang Wang; Li-li Xu; Hai-bin Wang; Pei-ling Li; Zhi-yong Guan; Fa-di Chen (Euphytica, 2013)

Bacillus abyssalis sp. nov., isolated from a sediment of the South China Sea - Zhi-Qing You; Jie Li; Sheng Qin; Xin-Peng Tian; Fa-Zuo Wang; Si Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2013)

Application of portable gas chromatography-photo ionization detector combined with headspace sampling for field analysis of benzene, toluene, ethylbenzene, and xylene in soils - You-Ya Zhou; Ji-Fang Yu; Zeng-Guang Yan; Chao-Yan Zhang; Ya-Bo Xie; Li-Qiang Ma; Qing-Bao Gu; Fa-Sheng Li (Environmental Monitoring and Assessment, 2013)

Coexpression of ScNHX1 and ScVP in Transgenic Hybrids Improves Salt and Saline-Alkali Tolerance in Alfalfa (Medicago sativa L.) - Liang Liu; Xiu-Duo Fan; Fa-Wei Wang; Nan Wang; Yuan-Yuan Dong; Xiu-Ming Liu; Jing Yang; Yan-Fang Wang; Hai-Yan Li (Journal of Plant Growth Regulation, 2013)

Spatial patterns and climate drivers of carbon fluxes in terrestrial ecosystems of China - Gui‐Rui Yu; Xian‐Jin Zhu; Yu‐Ling Fu; Hong‐Lin He; Qiu‐Feng Wang; Xue‐Fa Wen; Xuan‐Ran Li; Lei‐Ming Zhang; Li Zhang; Wen Su; Sheng‐Gong Li; Xiao‐Min Sun; et al. (Global Change Biology, 2013)
Understanding the dynamics and underlying mechanism of carbon exchange between terrestrial ecosystems and the atmosphere is one of the key issues in global change research. In this study, we quantified the carbon fluxes in different terrestrial ecosystems in China, and analyzed their spatial variation and environmental drivers based on the long‐term observation data of China FLUX sites and the published data from other flux sites in China. The results indicate that gross ecosystem productivity ( GEP ), ecosystem respiration ( ER ), and net ecosystem productivity ( NEP ) of terrestrial ecosystems in China showed a significantly latitudinal pattern, declining linearly with the increase of latitude. However, GEP , ER , and NEP did not present a clear longitudinal pattern. The carbon sink functional areas of terrestrial ecosystems in China were mainly located in the subtropical and temperate forests, coastal wetlands in eastern China, the temperate meadow steppe in the northeast China, and the alpine meadow in eastern edge of Qinghai‐Tibetan Plateau. The forest ecosystems had stronger carbon sink than grassland ecosystems. The spatial patterns of GEP and ER in China were mainly determined by mean annual precipitation ( MAP ) and mean annual temperature ( MAT ), whereas the spatial variation in NEP was largely explained by MAT . The combined effects of MAT and MAP explained 79%, 62%, and 66% of the spatial variations in GEP , ER , and NEP , respectively. The GEP , ER , and NEP in different ecosystems in China exhibited ‘positive coupling correlation’ in their spatial patterns. Both ER and NEP were significantly correlated with GEP , with 68% of the per‐unit GEP contributed to ER and 29% to NEP . MAT and MAP affected the spatial patterns of ER and NEP mainly by their direct effects on the spatial pattern of GEP .

Toxicity of CdTe QDs with different sizes targeted to HSA investigated by two electrochemical methods - Zi-Qiang Xu; Lu Lai; Dong-Wei Li; Ran Li; Chen Xiang; Feng-Lei Jiang; Shao-Fa Sun; Yi Liu (Molecular Biology Reports, 2013)

Metabolic Changes Detected by Ex Vivo High Resolution 1H NMR Spectroscopy in the Striatum of 6-OHDA-Induced Parkinson’s Rat - Hong-Chang Gao; Huan Zhu; Cai-Yong Song; Li Lin; Yun Xiang; Zhi-Han Yan; Guang-Hui Bai; Fa-Qing Ye; Xiao-Kun Li (Molecular Neurobiology, 2013)

Late Quaternary (30.7–9.0 cal ka BP) vegetation history in Central Asia inferred from pollen records of Lake Balikun, northwest China - Cheng-Bang An; Shi-Chen Tao; Jiaju Zhao; Fa-Hu Chen; Yanbin Lv; Weimiao Dong; Hu Li; Yongtao Zhao; Ming Jin; Zongli Wang (Journal of Paleolimnology, 2013)

Tectonic mechanism of the Suining (Ms5.0) earthquake, center of Sichuan Basin, China - Rong-jun Zhou; Yong Li; Laurence Svirchev; Yong-jiu Zhang; Deng-fa He; Yu-lin He; Pei-lin Zhao; Zan-jun Wang; Feng Long; Jin-rong Su; Shi-yuan Wang; Ming-jian Liang; et al. (Journal of Mountain Science, 2013)

Phylogenetic diversity of bacterial endophytes of Panax notoginseng with antagonistic characteristics towards pathogens of root-rot disease complex - Li Ma; Yong Hong Cao; Ming Hui Cheng; Ying Huang; Ming He Mo; Yong Wang; Jian Zhong Yang; Fa Xiang Yang (Antonie van Leeuwenhoek, 2013)

A New Elasto-Viscoplastic Damage Model Combined with the Generalized Hoek–Brown Failure Criterion for Bedded Rock Salt and its Application - Lin-jian Ma; Xin-yu Liu; Qin Fang; Hong-fa Xu; Hui-min Xia; Er-bing Li; Shi-gang Yang; Wen-pei Li (Rock Mechanics and Rock Engineering, 2013)

Effects of AM Inoculation and Organic Amendment, Alone or in Combination, on Growth, P Nutrition, and Heavy-Metal Uptake of Tobacco in Pb-Cd-Contaminated Soil - Fa Yuan Wang; Ling Wang; Zhao Yong Shi; You Jun Li; Zhi Mei Song (Journal of Plant Growth Regulation, 2012)

Conditional QTL mapping of protein content in wheat with respect to grain yield and its components - LIN WANG; FA CUI; JINPING WANG; LI JUN; ANMING DING; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2012)

VEGF upregulates VEGF receptor-2 on human outer root sheath cells and stimulates proliferation through ERK pathway - Wei Li; Zhong-Fa Lu; Xiao-Yong Man; Chun-Ming Li; Jiong Zhou; Jia-Qi Chen; Xiao-Hong Yang; Xian-Jie Wu; Sui-Qing Cai; Min Zheng (Molecular Biology Reports, 2012)

Signal-purity-spectrum-based colored deconvolution - Guo-Fa Li; Geng-Xin Peng; Ying Yue; Wan-Li Wang; Yong-Fu Cui (Applied Geophysics, 2012)

Landslides and catchment sedimentation in the Ta-Chia River influenced by the 1999 Taiwan Chi-Chi earthquake - Keh-Jian Shou; Li-Yuan Fei; Jiin-Fa Lee; Cheng-Yueh Wei; Sheng-Tsi Huang; You-Chang Lin (International Journal of Remote Sensing, 2012)

QTL detection of seven spike-related traits and their genetic correlations in wheat using two related RIL populations - Fa Cui; Anming Ding; Jun Li; Chunhua Zhao; Lin Wang; Xiuqin Wang; Xiaolei Qi; Xingfeng Li; Guoyu Li; Jurong Gao; Honggang Wang (Euphytica, 2012)

S-nitrosylation of c-Src via NMDAR-nNOS module promotes c-Src activation and NR2A phosphorylation in cerebral ischemia/reperfusion - Li-Juan Tang; Chong Li; Shu-Qun Hu; Yong-Ping Wu; Yan-Yan Zong; Chang-Cheng Sun; Fa Zhang; Guang-Yi Zhang (Molecular and Cellular Biochemistry, 2012)

Seasonal Changes in the Genetic Diversity of Two Rodent Populations, Midday Gerbil (Meriones meridianus) and Northern Three-Toed Jerboa (Dipus sagitta), Detected by ISSR - Rong Zhou; You Li; Jia-Qi Li; Nai-Fa Liu (Biochemical Genetics, 2012)

Janibacter alkaliphilus sp. nov., isolated from coral Anthogorgia sp - Jie Li; Li-Juan Long; Ling–Ling Yang; Ying Xu; Fa-Zuo Wang; Qing-Xin Li; Si Zhang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Lysinibacillus mangiferahumi sp. nov., a new bacterium producing nematicidal volatiles - Ling-Ling Yang; Ying Huang; Jie Liu; Li Ma; Ming-He Mo; Wen-Jun Li; Fa-Xiang Yang (Antonie van Leeuwenhoek, 2012)

A high-accuracy method for filling voids and its verification - Tian-Xiang Yue; Chuan-FA Chen; Bai-Lian Li (International Journal of Remote Sensing, 2012)

Double-stranded Let-7 mimics, potential candidates for cancer gene therapy - Qi-zhao Wang; Ying-hui Lv; Yu-hua Gong; Zhao-fa Li; William Xu; Yong Diao; Ruian Xu (Journal of Physiology and Biochemistry, 2012)

Transdifferentiation of human adipose-derived stem cells into urothelial cells: potential for urinary tract tissue engineering - Jian-Guo Shi; Wei-Jun Fu; Xiao-Xiong Wang; Yong-De Xu; Gang Li; Bao-Fa Hong; Kun Hu; Fu-Zhai Cui; Yan Wang; Xu Zhang (Cell and Tissue Research, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

Alternaria toxin-induced resistance against rose aphids and olfactory response of aphids to toxin-induced volatiles of rose plants - Fa-zhong Yang; Li Li; Bin Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Protein sequence analysis based on hydropathy profile of amino acids - Xiao-li Xie; Li-fei Zheng; Ying Yu; Li-ping Liang; Man-cai Guo; John Song; Zhi-fa Yuan (Journal of Zhejiang University-SCIENCE B, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Significant genetic differentiation between native and introduced silver carp (Hypophthalmichthys molitrix) inferred from mtDNA analysis - Si-Fa Li; Jia-Wei Xu; Qi-Ling Yang; Cheng-Hui Wang; Duane C. Chapman; Guoqing Lu (Environmental Biology of Fishes, 2011)

Wheat kernel dimensions: how do they contribute to kernel weight at an individual QTL level? - FA CUI; ANMING DING; JUN LI; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; XIUQIN WANG; LIN WANG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2011)

PKCα take part in CCR7/NF-κB autocrine signaling loop in CCR7-positive squamous cell carcinoma of head and neck - Zhao Zhen-jin; Li Peng; Liu Fa-yu; Sun Liyan; Sun Chang-fu (Molecular and Cellular Biochemistry, 2011)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

A new QTL for resistance to Fusarium ear rot in maize - Zhi-Min Li; Jun-Qiang Ding; Rui-Xia Wang; Jia-Fa Chen; Xiao-Dong Sun; Wei Chen; Wei-Bin Song; Hua-Fang Dong; Xiao-Dong Dai; Zong-Liang Xia; Jian-Yu Wu (Journal of Applied Genetics, 2011)

The Mechanism of the Molecular Interaction between Cerium (III) and Ribulose-1,5-Bisphosphate Carboxylase/Oxygenase (Rubisco) - Chao Liu; Fa-shui Hong; Ye Tao; Tao Liu; Ya-ning Xie; Jian-hua Xu; Zhong-rui Li (Biological Trace Element Research, 2011)

Methyl-1-hydroxy-2-naphthoate, a novel naphthol derivative, inhibits lipopolysaccharide-induced inflammatory response in macrophages via suppression of NF-κB, JNK and p38 MAPK pathways - Jun-Yan Zhang; Hong Jin; Guang-Fa Wang; Peng-Jiu Yu; Shao-Yu Wu; Zheng-Guang Zhu; Zhong-Huang Li; Yuan-Xin Tian; Wei Xu; Jia-Jie Zhang; Shu-Guang Wu (Inflammation Research, 2011)

Effects of temporarily disrupting BBB on activity-induced manganese-dependent functional MRI - Zhiqiang Fa; Run Zhang; Peng Li; Jing Zhang; Peng Zhang; Shaofang Zhu; Qu Wu; Fanheng Huang; Yanping Liu; Lujun Yang; Haigang Chang; Zhibo Wen; et al. (Brain Imaging and Behavior, 2011)

Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves) - Hsu‐Chun Wu; Rong‐Chien Lin; Hsin‐Yi Hung; Chia‐Fen Yeh; Jui‐Hua Chu; Xiao‐Jun Yang; Chiou‐Ju Yao; Fa‐Sheng Zou; Cheng‐Te Yao; Shou‐Hsien Li; Fu‐Min Lei (Zoologica Scripta, 2011)
Wu, H.‐C., Lin, R.‐C., Hung, H.‐Y., Yeh, C.‐F., Chu, J.‐H., Yang, X.‐J., Yao, C.‐J., Zou, F.‐S., Yao, C.‐T., Li, S.‐H. & Lei, F.‐M. (2011). Molecular and morphological evidences reveal a cryptic species in the Vinaceous Rosefinch Carpodacus vinaceus (Fringillidae; Aves). — Zoologica Scripta, 40 , 468–478. The Vinaceous Rosefinch ( Carpodacus vinaceus ) is endemic in East Asia with two recognized subspecies – C. v. vinaceus , distributed along the eastern edge of the Tibetan Plateau and the Himalayas, and C. v. formosanus , restricted to Taiwan’s Central Mountain Range. As reflected in a controversial taxonomic history, this vastly disjunctive distribution pattern suggests that the subspecies, having been isolated from each other for a long time, might have diverged, challenging the current taxonomic treatment and calling for possible species delimitation. Sequences of two mitochondrial fragments (mtDNA) and two Z‐linked nuclear loci (zDNA) were used to reconstruct the intraspecific phylogeny of C. vinaceous . The mtDNA tree shows that the two subspecies of the vinaceous rosefinch form two exclusively monophyletic clades. All but one zDNA sequences from the nominate subspecies and C. v. formosanus also formed exclusively monophyletic clades (the exceptional zDNA sequence from C. v. vinaceous formed a weakly supported clade with two outgroup species). Moreover, by conducting quantitative comparisons of morphometric traits and male plumage coloration, we found that the two subspecies exhibit distinguishable morphological differences. All the evidence therefore suggests that C. v. formosanus is a cryptic species and that its taxonomic status should be restored to full species. Molecular dating suggests that the two sibling rosefinches split 1.7 ± 0.2 million years ago, providing a point estimate for the historical connectivity of biota between eastern Tibet‐Himalayas and montane Taiwan.

Supplemental Selenium Alleviates the Toxic Effects of Excessive Iodine on Thyroid - Jian Xu; Xiao-Li Liu; Xue-Feng Yang; Huai-Lan Guo; Li-na Zhao; Xiu-Fa Sun (Biological Trace Element Research, 2011)

Expression patterns of prion protein gene in differential genotypes sheep: quantification using molecular beacon real-time RT-PCR - Chuan Wang; Run Wu; Fa-Di Li; Lei Liu; Xiao-Li Zhang; Chun-Lin Zhao; Xiao-Long Diao; Hong-Wei Guan (Virus Genes, 2011)

Conditional QTL mapping for plant height with respect to the length of the spike and internode in two mapping populations of wheat - Fa Cui; Jun Li; Anming Ding; Chunhua Zhao; Lin Wang; Xiuqin Wang; Sishen Li; Yinguang Bao; Xingfeng Li; Deshun Feng; Lingrang Kong; Honggang Wang (Theoretical and Applied Genetics, 2011)

A checklist of parasitic nematodes from marine fishes of China - Wen-feng Peng; Sheng-fa Liu; Bing-li Wang; Mei-mei Wei (Systematic Parasitology, 2011)

Overcoming pre-fertilization barriers in the wide cross between Chrysanthemum grandiflorum (Ramat.) Kitamura and C. nankingense (Nakai) Tzvel. by using special pollination techniques - Chun-Qing Sun; Zhi-Zhe Huang; Yan-Li Wang; Fa-Di Chen; Nian-Jun Teng; Wei-Min Fang; Zhao-Lei Liu (Euphytica, 2011)

Dwarf apple MbDREB1 enhances plant tolerance to low temperature, drought, and salt stress via both ABA-dependent and ABA-independent pathways - Wei Yang; Xiao-Dan Liu; Xiao-Juan Chi; Chang-Ai Wu; Yan-Ze Li; Li-Li Song; Xiu-Ming Liu; Yan-Fang Wang; Fa-Wei Wang; Chuang Zhang; Yang Liu; Jun-Mei Zong; et al. (Planta, 2011)

Arbuscular mycorrhizal fungal community structure and diversity in response to long-term fertilization: a field case from China - Fa Yuan Wang; Jun Li Hu; Xian Gui Lin; Sheng Wu Qin; Jun Hua Wang (World Journal of Microbiology and Biotechnology, 2011)

Interleukin-10 gene polymorphisms in association with susceptibility to chronic hepatitis C virus infection: a meta-analysis study - Li-Zhou Zhang; Tian-Chen Zhang; Fa-Ming Pan; Zhen-Hua Zhang; Xu Li (Archives of Virology, 2010)

Derived vascular endothelial cells induced by mucoepidermoid carcinoma cells: 3-dimensional collagen matrix model - Sen Yang; Li-juan Guo; Qing-hong Gao; Ming Xuan; Ke Tan; Qiang Zhang; Yu-ming Wen; Chang-mei Wang; Xiu-fa Tang; Xiao-yi Wang (Journal of Zhejiang University-SCIENCE B, 2010)

Ecotoxicity assessment of aged petroleum sludge using a suite of effects-based end points in earthworm Eisenia fetida - Shi-Jie Wang; Zeng-Guang Yan; Guan-Lin Guo; Gui-Lan Lu; Qun-Hui Wang; Fa-Sheng Li (Environmental Monitoring and Assessment, 2010)

Angiotensin-converting enzyme 2 (ACE2) proteins of different bat species confer variable susceptibility to SARS-CoV entry - Yuxuan Hou; Cheng Peng; Meng Yu; Yan Li; Zhenggang Han; Fang Li; Lin-Fa Wang; Zhengli Shi (Archives of Virology, 2010)

Remote chlorophyll- a retrieval in Case-II waters using an improved model and IRS-P6 satellite data - Jing-Ping Xu; Fang Li; Bai Zhang; Xing-Fa Gu; Tao Yu (International Journal of Remote Sensing, 2010)

A novel model for assessing the pore structure of tight sands and its application - Chao-Liu Li; Can-Can Zhou; Xia Li; Fa-Long Hu; Li Zhang; Wei-Jun Wang (Applied Geophysics, 2010)

Can the soil seed bank contribute to revegetation of the drawdown zone in the Three Gorges Reservoir Region? - Zhi-Jun Lu; Lian-Fa Li; Ming-Xi Jiang; Han-Dong Huang; Da-Chuan Bao (Plant Ecology, 2010)

Neural circuits and temporal plasticity in hindlimb representation of rat primary somatosensory cortex: revisited by multi-electrode array on brain slices - Dan-Dan Wang; Zhen Li; Ying Chang; Rui-Rui Wang; Xue-Feng Chen; Zhen-Yu Zhao; Fa-Le Cao; Jian-Hui Jin; Ming-Gang Liu; Jun Chen (Neuroscience Bulletin, 2010)

Analysis of complicated structure seismic wave fields - Hui Zhou; Shang-Xu Wang; Guo-Fa Li; Jin-Song Shen (Applied Geophysics, 2010)

Modeling air gun signatures in marine seismic exploration considering multiple physical factors - Guo-Fa Li; Ming-Qiang Cao; Hao-Lin Chen; Cheng-Zhou Ni (Applied Geophysics, 2010)

Remote-sensing reflectance characteristics of highly turbid estuarine waters – a comparative experiment of the Yangtze River and the Yellow River - Fang Shen; MHD. Suhyb Salama; Yun-Xuan Zhou; Jiu-Fa Li; Zhongbo Su; Ding-Bo Kuang (International Journal of Remote Sensing, 2010)

Potential water sources for Late Quaternary Megalake Jilantai-Hetao, China, inferred from mollusk shell 87Sr/86Sr ratios - Yu-Xin Fan; Fa-Hu Chen; Guo-Xiao Wei; David B. Madsen; Charles G. Oviatt; Hui Zhao; Xi Chun; Li-Ping Yang; Tian-Lai Fan; Guo-Qiang Li (Journal of Paleolimnology, 2010)

Groundwater discharge to the Changjiang River, China, during the drought season of 2006: effects of the extreme drought and the impoundment of the Three Gorges Dam - Zhi-jun Dai; Jin-zhou Du; Ao Chu; Jiu-fa Li; Ji-yu Chen; Xiao-ling Zhang (Hydrogeology Journal, 2010)

Increased serum interleukin 17 in patients with systemic lupus erythematosus - Xue-Fei Zhao; Hai-Feng Pan; Hui Yuan; Wen-Hui Zhang; Xiang-Pei Li; Gui-Hong Wang; Guo-Cui Wu; Hong Su; Fa-Ming Pan; Wen-Xian Li; Lian-Hong Li; Guo-Ping Chen; et al. (Molecular Biology Reports, 2010)

Calling Behavior and Rhythms of Sex Pheromone Production in the Black Cutworm Moth in China - Yu-yong Xiang; Mao-fa Yang; Zi-zhong Li (Journal of Insect Behavior, 2010)

Provenance and thermal history of the Bayan Har Group in the western‐central Songpan–Ganzi–Bayan Har terrane: Implications for tectonic evolution of the northern Tibetan Plateau - Guo‐Can Wang; Robert P. Wintsch; John I. Garver; Mary Roden‐Tice; She‐Fa Chen; Ke‐Xin Zhang; Qi‐Xiang Lin; Yun‐Hai Zhu; Shu‐Yuan Xiang; De‐Wei Li (Island Arc, 2009)
Triassic turbidites dominate the Songpan–Ganzi–Bayan Har (SGBH) terrane of the northern Tibetan Plateau. U‐Pb dating on single detrital zircon grains from the Triassic Bayan Har Group turbidites yield peaks at 400–500 m.y., 900–1000 m.y., 1800–1900 m.y., and 2400–2500 m.y., These results are consistent with recently published U‐Pb zircon ages of pre‐Triassic bedrock in the East Kunlun, Altyn, Qaidam, Qilian and Alaxa areas to the north, suggesting that provenance of the Bayan Har Group may include these rocks. The similarities in the compositions of the lithic arkosic sandstones of the Bayan Har Group with the sandstones of the Lower‐Middle Triassic formations in the East Kunlun terrane to the north also suggests a common northern provenance for both. A well exposed angular unconformity between the Carboniferous–Middle Permian mélange sequences and the overlying Upper Permian or Triassic strata indicates that regional deformation occurred between the Middle and Late Permian. This deformation may have been the result of a soft collision between the Qiangtang terrane and the North China Plate and the closure of the Paleo‐Tethyan oceanic basin. The Bayan Har Group turbidites were then deposited in a re‐opened marine basin on a shelf environment. Fission‐track dating of detrital zircons from the Bayan Har Group sandstones revealed pre‐ and post‐depositional age components, suggesting that the temperatures did not reach the temperatures necessary to anneal retentive zircon fission tracks (250–300°C). A 282–292 m.y. peak age defined by low U concentration, retentive zircons likely reflects a northern granitic source. Euhedral zircons from two lithic arkoses with abundant volcanic fragments in the southern area yielded a ∼237 m.y. zircon fission track (ZFT) peak age, likely recording the maximum age of deposition. A dominant post‐depositional 170–185 m.y. ZFT peak age suggests peak temperatures were reached in the Early Jurassic. Some samples appear to record a younger thermal event at ∼140 m.y., a short lived event that apparently affected only the least retentive zircons.

Meiosis and pollen germinability in small-flowered anemone type chrysanthemum cultivars - Fa-Di Chen; Feng-Tong Li; Su-Mei Chen; Zhi-Yong Guan; Wei-Min Fang (Plant Systematics and Evolution, 2009)

Intercellular adhesion molecule-1 gene K469E polymorphism and ischemic stroke: a case-control study in a Chinese population - Xiao Xia Li; Jian Ping Liu; Jin Quan Cheng; Sheng Hong Han; Yi Jie Geng; Sheng Wei; Shi Tong Gao; Da Na Huang; Shao Fa Nie (Molecular Biology Reports, 2009)

Effects of long-term fertilization and mulch on soil fertility in contour hedgerow systems: A case study on steeplands from the Three Gorges Area, China - Zhi-Hua Shi; Li-Ding Chen; Chong-Fa Cai; Zhao-Xia Li; Guo-Hua Liu (Nutrient Cycling in Agroecosystems, 2009)

The effects of land use change on environmental quality in the red soil hilly region, China: A case study in Xianning County - Zhi-Hua Shi; Li-Ding Chen; Jun-Ping Hao; Tian-Wei Wang; Chong-Fa Cai (Environmental Monitoring and Assessment, 2009)

Short hairpin RNA targeting NP mRNA inhibiting Newcastle disease virus production and other viral structural mRNA transcription - Hua Yue; Shu Deng; Fa-long Yang; Ding-fei Li; An-jing Fu; Fan Yang; Cheng Tang (Virus Genes, 2009)

Karyotype and meiotic analyses of six species in the subtribe Chrysantheminae - Jian Li; Su-Mei Chen; Fa-Di Chen; Wei-Min Fang (Euphytica, 2008)

Environmental controls over carbon exchange of three forest ecosystems in eastern China - GUI‐RUI YU; LEI‐MING ZHANG; XIAO‐MIN SUN; YU‐LING FU; XUE‐FA WEN; QIU‐FENG WANG; SHENG‐GONG LI; CHUAN‐YOU REN; XIA SONG; YUN‐FEN LIU; SHI‐JIE HAN; JUN‐HUA YAN (Global Change Biology, 2008)
Net ecosystem productivity (NEP) was continuously measured using the eddy covariance (EC) technique from 2003 to 2005 at three forest sites of ChinaFLUX. The forests include Changbaishan temperate mixed forest (CBS), Qianyanzhou subtropical coniferous plantation (QYZ), and Dinghushan subtropical evergreen broad‐leaved forest (DHS). They span wide ranges of temperature and precipitation and are influenced by the eastern Asian monsoon climate to varying extent. In this study, we estimated ecosystem respiration (RE) and gross ecosystem productivity (GEP). Comparison of ecosystem carbon exchange among the three forests shows that RE was mainly determined by temperature, with the forest at CBS exhibiting the highest temperature sensitivity among the three ecosystems. The RE was highly dependent on GEP across the three forests, and the ratio of RE to GEP decreased along the North–South Transect of Eastern China (NSTEC) (i.e. from the CBS to the DHS), with an average of 0.77 ± 0.06. Daily GEP was mainly influenced by temperature at CBS, whereas photosynthetic photon flux density was the dominant factor affecting the daily GEP at both QYZ and DHS. Temperature mainly determined the pattern of the interannual variations of ecosystem carbon exchange at CBS. However, water availability primarily controlled the interannual variations of ecosystem carbon exchange at QYZ. At DHS, NEP attained the highest values at the beginning of the dry seasons (autumn) rather than the rainy seasons (summer), probably because insufficient radiation and frequent fog during the rainy seasons hindered canopy photosynthesis. All the three forest ecosystems acted as a carbon sink from 2003 to 2005. The annual average values of NEP at CBS, QYZ, and DHS were 259 ± 19, 354 ± 34, and 434 ± 66 g C m −2 yr −1 , respectively. The slope of NEP that decreased with increasing latitude along the NSTEC was markedly different from that observed on the forest transect in the European continent. Long‐term flux measurements over more forest ecosystems along the NSTEC will further help verify such a difference between the European forest transect and the NSTEC and provide insights into the responses of ecosystem carbon exchange to climate change in China.

Fluorescent co-localization of PTS1 and PTS2 and its application in analysis of the gene function and the peroxisomal dynamic in Magnaporthe oryzae - Jiao-yu Wang; Xiao-yan Wu; Zhen Zhang; Xin-fa Du; Rong-yao Chai; Xiao-hong Liu; Xue-qin Mao; Hai-ping Qiu; Yan-li Wang; Fu-cheng Lin; Guo-chang Sun (Journal of Zhejiang University-SCIENCE B, 2008)

Mitochondrial anchoring of PKCα by PICK1 confers resistance to etoposide-induced apoptosis - Wei-Li Wang; Sheau-Farn Yeh; Eagle Yi-Kung Huang; Yu-Ling Lu; Chun-Fa Wang; Chi-Ying F. Huang; Wey-Jinq Lin (Apoptosis, 2007)

Anti-hepatitis B activities of ganoderic acid from Ganoderma lucidum - Yan-Qun Li; Shun-Fa Wang (Biotechnology Letters, 2006)

Weathering mechanism of the Cretaceous argillaceous siltstone caverns, Longyou, China - Gai-mei Guo; Li-hui Li; Zhi-fa Yang; Bo Tao; Yong-xin Qu; Jian Zheng (Bulletin of Engineering Geology and the Environment, 2005)

The impact of NiO on microstructure and electrical property of solid oxide fuel cell anode - Yan Li; Zhong-yang Luo; Chun-jiang Yu; Dan Luo; Zhu-an Xu; Ke-fa Cen (Journal of Zhejiang University-SCIENCE B, 2005)

A Water Budget Model for the Yun-Lin Plain, Taiwan - Jin-Fa Chen; Cheng-Haw Lee; Tian-Chyi J. Yeh; Jin-Li Yu (Water Resources Management, 2005)

Analysis of habitat pattern change of red-crowned cranes in the Liaohe delta using Spatial Diversity Index - Ling Wang; Xiu-zhen Li; Yuan-man Hu; Du-fa Guo (Chinese Geographical Science, 2003)

Structural studies of the glycopeptides of B-chain of cinnamomin – a type II ribosome-inactivating protein by nuclear magnetic resonance - Zheng Pu; Yiming Li; Fa-jian Hou; Fahu He; Naixia Zhang; Houming Wu; Wang-Yi Liu (Glycoconjugate Journal, 2000)

Identification of two chilling-regulated 1-aminocyclopropane- 1-carboxylate synthase genes from citrus (Citrus sinensis Osbeck) fruit - Wai Shing Wong; Wen Ning; Pei Lin Xu; Shain Dow Kung; Shang Fa Yang; Ning Li (Plant Molecular Biology, 1999)

Allelopathic Potential of Acacia confusa and Related Species in Taiwan - Chang-Hung Chou; Chiu-Yu Fu; Shin-Yi Li; Yu-Fa Wang (Journal of Chemical Ecology, 1998)